Timing, variability and cross-protection in bacteria – insights from dynamic gene expression responses to antibiotics - Mitosch, Karin
Antibiotics have diverse effects on bacteria, including massive changes in bacterial gene expression. Whereas the gene expression changes under many antibiotics have been measured, the temporal organization of these responses and their dependence on the bacterial growth rate are unclear. As described in Chapter 1, we quantified the temporal gene expression changes in the bacterium Escherichia coli in response to the sudden exposure to antibiotics using a fluorescent reporter library and a robotic system. Our data show temporally structured gene expression responses, with response times for individual genes ranging from tens of minutes to several hours. We observed that many stress response genes were activated in response to antibiotics. As certain stress responses cross-protect bacteria from other stressors, we then asked whether cellular responses to antibiotics have a similar protective role in Chapter 2. Indeed, we found that the trimethoprim-induced acid stress response protects bacteria from subsequent acid stress. We combined microfluidics with time-lapse imaging to monitor survival, intracellular pH, and acid stress response in single cells. This approach revealed that the variable expression of the acid resistance operon gadBC strongly correlates with single-cell survival time. Cells with higher gadBC expression following trimethoprim maintain higher intracellular pH and survive the acid stress longer. Overall, we provide a way to identify single-cell cross-protection between antibiotics and environmental stressors from temporal gene expression data, and show how antibiotics can increase bacterial fitness in changing environments. While gene expression changes to antibiotics show a clear temporal structure at the population-level, it is unclear whether this clear temporal order is followed by every single cell. Using dual-reporter strains described in Chapter 3, we measured gene expression dynamics of promoter pairs in the same cells using microfluidics and microscopy. Chapter 4 shows that the oxidative stress response and the DNA stress response showed little timing variability and a clear temporal order under the antibiotic nitrofurantoin. In contrast, the acid stress response under trimethoprim ran independently from all other activated response programs including the DNA stress response, which showed particularly high timing variability in this stress condition. In summary, this approach provides insight into the temporal organization of gene expression programs at the single-cell level and suggests dependencies between response programs and the underlying variability-introducing mechanisms. Altogether, this work advances our understanding of the diverse effects that antibiotics have on bacteria. These results were obtained by taking into account gene expression dynamics, which allowed us to identify general principles, molecular mechanisms, and dependencies between genes. Our findings may have implications for infectious disease treatments, and microbial communities in the human body and in nature.

Noisy response to antibiotic stress predicts subsequent single cell survival in an acidic environment - Mitosch, Karin; Rieckh, Georg; Bollenbach, Tobias (Cell Systems)
Antibiotics elicit drastic changes in microbial gene expression, including the induction of stress response genes. While certain stress responses are known to “cross-protect” bacteria from other stressors, it is unclear whether cellular responses to antibiotics have a similar protective role. By measuring the genome-wide transcriptional response dynamics of Escherichia coli to four antibiotics, we found that trimethoprim induces a rapid acid stress response that protects bacteria from subsequent exposure to acid. Combining microfluidics with time-lapse imaging to monitor survival and acid stress response in single cells revealed that the noisy expression of the acid resistance operon gadBC correlates with single-cell survival. Cells with higher gadBC expression following trimethoprim maintain higher intracellular pH and survive the acid stress longer. The seemingly random single-cell survival under acid stress can therefore be predicted from gadBC expression and rationalized in terms of GadB/C molecular function. Overall, we provide a roadmap for identifying the molecular mechanisms of single-cell cross-protection between antibiotics and other stressors.

Algorithmic advances in program analysis and their applications - Pavlogiannis, Andreas
This dissertation focuses on algorithmic aspects of program verification, and presents modeling and complexity advances on several problems related to the static analysis of programs, the stateless model checking of concurrent programs, and the competitive analysis of real-time scheduling algorithms. Our contributions can be broadly grouped into five categories. Our first contribution is a set of new algorithms and data structures for the quantitative and data-flow analysis of programs, based on the graph-theoretic notion of treewidth. It has been observed that the control-flow graphs of typical programs have special structure, and are characterized as graphs of small treewidth. We utilize this structural property to provide faster algorithms for the quantitative and data-flow analysis of recursive and concurrent programs. In most cases we make an algebraic treatment of the considered problem, where several interesting analyses, such as the reachability, shortest path, and certain kind of data-flow analysis problems follow as special cases. We exploit the constant-treewidth property to obtain algorithmic improvements for on-demand versions of the problems, and provide data structures with various tradeoffs between the resources spent in the preprocessing and querying phase. We also improve on the algorithmic complexity of quantitative problems outside the algebraic path framework, namely of the minimum mean-payoff, minimum ratio, and minimum initial credit for energy problems. Our second contribution is a set of algorithms for Dyck reachability with applications to data-dependence analysis and alias analysis. In particular, we develop an optimal algorithm for Dyck reachability on bidirected graphs, which are ubiquitous in context-insensitive, field-sensitive points-to analysis. Additionally, we develop an efficient algorithm for context-sensitive data-dependence analysis via Dyck reachability, where the task is to obtain analysis summaries of library code in the presence of callbacks. Our algorithm preprocesses libraries in almost linear time, after which the contribution of the library in the complexity of the client analysis is (i)~linear in the number of call sites and (ii)~only logarithmic in the size of the whole library, as opposed to linear in the size of the whole library. Finally, we prove that Dyck reachability is Boolean Matrix Multiplication-hard in general, and the hardness also holds for graphs of constant treewidth. This hardness result strongly indicates that there exist no combinatorial algorithms for Dyck reachability with truly subcubic complexity. Our third contribution is the formalization and algorithmic treatment of the Quantitative Interprocedural Analysis framework. In this framework, the transitions of a recursive program are annotated as good, bad or neutral, and receive a weight which measures the magnitude of their respective effect. The Quantitative Interprocedural Analysis problem asks to determine whether there exists an infinite run of the program where the long-run ratio of the bad weights over the good weights is above a given threshold. We illustrate how several quantitative problems related to static analysis of recursive programs can be instantiated in this framework, and present some case studies to this direction. Our fourth contribution is a new dynamic partial-order reduction for the stateless model checking of concurrent programs. Traditional approaches rely on the standard Mazurkiewicz equivalence between traces, by means of partitioning the trace space into equivalence classes, and attempting to explore a few representatives from each class. We present a new dynamic partial-order reduction method called the Data-centric Partial Order Reduction (DC-DPOR). Our algorithm is based on a new equivalence between traces, called the observation equivalence. DC-DPOR explores a coarser partitioning of the trace space than any exploration method based on the standard Mazurkiewicz equivalence. Depending on the program, the new partitioning can be even exponentially coarser. Additionally, DC-DPOR spends only polynomial time in each explored class. Our fifth contribution is the use of automata and game-theoretic verification techniques in the competitive analysis and synthesis of real-time scheduling algorithms for firm-deadline tasks. On the analysis side, we leverage automata on infinite words to compute the competitive ratio of real-time schedulers subject to various environmental constraints. On the synthesis side, we introduce a new instance of two-player mean-payoff partial-information games, and show how the synthesis of an optimal real-time scheduler can be reduced to computing winning strategies in this new type of games.

The lac operon in the wild - Jesse, Fabienne
The lac operon is a classic model system for bacterial gene regulation, and has been studied extensively in E. coli, a classic model organism. However, not much is known about E. coli’s ecology and life outside the laboratory, in particular in soil and water environments. The natural diversity of the lac operon outside the laboratory, its role in the ecology of E. coli and the selection pressures it is exposed to, are similarly unknown. In Chapter Two of this thesis, I explore the genetic diversity, phylogenetic history and signatures of selection of the lac operon across 20 natural isolates of E. coli and divergent clades of Escherichia. I found that complete lac operons were present in all isolates examined, which in all but one case were functional. The lac operon phylogeny conformed to the whole-genome phylogeny of the divergent Escherichia clades, which excludes horizontal gene transfer as an explanation for the presence of functional lac operons in these clades. All lac operon genes showed a signature of purifying selection; this signature was strongest for the lacY gene. Lac operon genes of human and environmental isolates showed similar signatures of selection, except the lacZ gene, which showed a stronger signature of selection in environmental isolates. In Chapter Three, I try to identify the natural genetic variation relevant for phenotype and fitness in the lac operon, comparing growth rate on lactose and LacZ activity of the lac operons of these wild isolates in a common genetic background. Sequence variation in the lac promoter region, upstream of the -10 and -35 RNA polymerase binding motif, predicted variation in LacZ activity at full induction, using a thermodynamic model of polymerase binding (Tugrul, 2016). However, neither variation in LacZ activity, nor RNA polymerase binding predicted by the model correlated with variation in growth rate. Lac operons of human and environmental isolates did not differ systematically in either growth rate on lactose or LacZ protein activity, suggesting that these lac operons have been exposed to similar selection pressures. We thus have no evidence that the phenotypic variation we measured is relevant for fitness. To start assessing the effect of genomic background on the growth phenotype conferred by the lac operon, I compared growth on minimal medium with lactose between lac operon constructs and the corresponding original isolates, I found that maximal growth rate was determined by genomic background, with almost all backgrounds conferring higher growth rates than lab strain K12 MG1655. However, I found no evidence that the lactose concentration at which growth was half maximal depended on genomic background.

(The exact security of) Message authentication codes - Rybar, Michal
In this thesis we discuss the exact security of message authentications codes HMAC , NMAC , and PMAC . NMAC is a mode of operation which turns a fixed input-length keyed hash function f into a variable input-length function. A practical single-key variant of NMAC called HMAC is a very popular and widely deployed message authentication code (MAC). PMAC is a block-cipher based mode of operation, which also happens to be the most famous fully parallel MAC. NMAC was introduced by Bellare, Canetti and Krawczyk Crypto’96, who proved it to be a secure pseudorandom function (PRF), and thus also a MAC, under two assumptions. Unfortunately, for many instantiations of HMAC one of them has been found to be wrong. To restore the provable guarantees for NMAC , Bellare [Crypto’06] showed its security without this assumption. PMAC was introduced by Black and Rogaway at Eurocrypt 2002. If instantiated with a pseudorandom permutation over n -bit strings, PMAC constitutes a provably secure variable input-length PRF. For adversaries making q queries, each of length at most ` (in n -bit blocks), and of total length σ ≤ q` , the original paper proves an upper bound on the distinguishing advantage of O ( σ 2 / 2 n ), while the currently best bound is O ( qσ/ 2 n ). In this work we show that this bound is tight by giving an attack with advantage Ω( q 2 `/ 2 n ). In the PMAC construction one initially XORs a mask to every message block, where the mask for the i th block is computed as τ i := γ i · L , where L is a (secret) random value, and γ i is the i -th codeword of the Gray code. Our attack applies more generally to any sequence of γ i ’s which contains a large coset of a subgroup of GF (2 n ). As for NMAC , our first contribution is a simpler and uniform proof: If f is an ε -secure PRF (against q queries) and a δ - non-adaptively secure PRF (against q queries), then NMAC f is an ( ε + `qδ )-secure PRF against q queries of length at most ` blocks each. We also show that this ε + `qδ bound is basically tight by constructing an f for which an attack with advantage `qδ exists. Moreover, we analyze the PRF-security of a modification of NMAC called NI by An and Bellare that avoids the constant rekeying on multi-block messages in NMAC and allows for an information-theoretic analysis. We carry out such an analysis, obtaining a tight `q 2 / 2 c bound for this step, improving over the trivial bound of ` 2 q 2 / 2 c . Finally, we investigate, if the security of PMAC can be further improved by using τ i ’s that are k -wise independent, for k > 1 (the original has k = 1). We observe that the security of PMAC will not increase in general if k = 2, and then prove that the security increases to O ( q 2 / 2 n ), if the k = 4. Due to simple extension attacks, this is the best bound one can hope for, using any distribution on the masks. Whether k = 3 is already sufficient to get this level of security is left as an open problem. Keywords: Message authentication codes, Pseudorandom functions, HMAC, PMAC.

The exact security of PMAC - Gazi, Peter; Pietrzak, Krzysztof Z; Rybar, Michal (IACR Transactions on Symmetric Cryptology)
PMAC is a simple and parallel block-cipher mode of operation, which was introduced by Black and Rogaway at Eurocrypt 2002. If instantiated with a (pseudo)random permutation over n-bit strings, PMAC constitutes a provably secure variable input-length (pseudo)random function. For adversaries making q queries, each of length at most l (in n-bit blocks), and of total length σ ≤ ql, the original paper proves an upper bound on the distinguishing advantage of Ο(σ2/2n), while the currently best bound is Ο (qσ/2n).In this work we show that this bound is tight by giving an attack with advantage Ω (q2l/2n). In the PMAC construction one initially XORs a mask to every message block, where the mask for the ith block is computed as τi := γi·L, where L is a (secret) random value, and γi is the i-th codeword of the Gray code. Our attack applies more generally to any sequence of γi’s which contains a large coset of a subgroup of GF(2n). We then investigate if the security of PMAC can be further improved by using τi’s that are k-wise independent, for k > 1 (the original distribution is only 1-wise independent). We observe that the security of PMAC will not increase in general, even if the masks are chosen from a 2-wise independent distribution, and then prove that the security increases to O(q<2/2n), if the τi are 4-wise independent. Due to simple extension attacks, this is the best bound one can hope for, using any distribution on the masks. Whether 3-wise independence is already sufficient to get this level of security is left as an open problem.

Reactivation of the hippocampal cognitive map in goal-directed spatial tasks - Xu, Haibing
The hippocampus is a key brain region for memory and notably for spatial memory, and is needed for both spatial working and reference memories. Hippocampal place cells selectively discharge in specific locations of the environment to form mnemonic represen tations of space. Several behavioral protocols have been designed to test spatial memory which requires the experimental subject to utilize working memory and reference memory. However, less is known about how these memory traces are presented in the hippo campus, especially considering tasks that require both spatial working and long -term reference memory demand. The aim of my thesis was to elucidate how spatial working memory, reference memory, and the combination of both are represented in the hippocampus. In this thesis, using a radial eight -arm maze, I examined how the combined demand on these memories influenced place cell assemblies while reference memories were partially updated by changing some of the reward- arms. This was contrasted with task varian ts requiring working or reference memories only. Reference memory update led to gradual place field shifts towards the rewards on the switched arms. Cells developed enhanced firing in passes between newly -rewarded arms as compared to those containing an unchanged reward. The working memory task did not show such gradual changes. Place assemblies on occasions replayed trajectories of the maze; at decision points the next arm choice was preferentially replayed in tasks needing reference memory while in the pure working memory task the previously visited arm was replayed. Hence trajectory replay only reflected the decision of the animal in tasks needing reference memory update. At the reward locations, in all three tasks outbound trajectories of the current arm were preferentially replayed, showing the animals’ next path to the center. At reward locations trajectories were replayed preferentially in reverse temporal order. Moreover, in the center reverse replay was seen in the working memory task but in the other tasks forward replay was seen. Hence, the direction of reactivation was determined by the goal locations so that part of the trajectory which was closer to the goal was reactivated later in an HSE while places further away from the goal were reactivated earlier. Altogether my work demonstrated that reference memory update triggers several levels of reorganization of the hippocampal cognitive map which are not seen in simpler working memory demand s. Moreover, hippocampus is likely to be involved in spatial decisions through reactivating planned trajectories when reference memory recall is required for such a decision.

Investigations into cell polarity and trafficking in the plant model Arabidopsis thaliana - Adamowski, Maciek
The thesis encompasses several topics of plant cell biology which were studied in the model plant Arabidopsis thaliana. Chapter 1 concerns the plant hormone auxin and its polar transport through cells and tissues. The highly controlled, directional transport of auxin is facilitated by plasma membrane-localized transporters. Transporters from the PIN family direct auxin transport due to their polarized localizations at cell membranes. Substantial effort has been put into research on cellular trafficking of PIN proteins, which is thought to underlie their polar distribution. I participated in a forward genetic screen aimed at identifying novel regulators of PIN polarity. The screen yielded several genes which may be involved in PIN polarity regulation or participate in polar auxin transport by other means. Chapter 2 focuses on the endomembrane system, with particular attention to clathrin-mediated endocytosis. The project started with identification of several proteins that interact with clathrin light chains. Among them, I focused on two putative homologues of auxilin, which in non-plant systems is an endocytotic factor known for uncoating clathrin-coated vesicles in the final step of endocytosis. The body of my work consisted of an in-depth characterization of transgenic A. thaliana lines overexpressing these putative auxilins in an inducible manner. Overexpression of these proteins leads to an inhibition of endocytosis, as documented by imaging of cargoes and clathrin-related endocytic machinery. An extension of this work is an investigation into a concept of homeostatic regulation acting between distinct transport processes in the endomembrane system. With auxilin overexpressing lines, where endocytosis is blocked specifically, I made observations on the mutual relationship between two opposite trafficking processes of secretion and endocytosis. In Chapter 3, I analyze cortical microtubule arrays and their relationship to auxin signaling and polarized growth in elongating cells. In plants, microtubules are organized into arrays just below the plasma membrane, and it is thought that their function is to guide membrane-docked cellulose synthase complexes. These, in turn, influence cell wall structure and cell shape by directed deposition of cellulose fibres. In elongating cells, cortical microtubule arrays are able to reorient in relation to long cell axis, and these reorientations have been linked to cell growth and to signaling of growth-regulating factors such as auxin or light. In this chapter, I am addressing the causal relationship between microtubule array reorientation, growth, and auxin signaling. I arrive at a model where array reorientation is not guided by auxin directly, but instead is only controlled by growth, which, in turn, is regulated by auxin.

Complexity of constraint satisfaction - Rolinek, Michal
An instance of the Constraint Satisfaction Problem (CSP) is given by a finite set of variables, a finite domain of labels, and a set of constraints, each constraint acting on a subset of the variables. The goal is to find an assignment of labels to its variables that satisfies all constraints (or decide whether one exists). If we allow more general “soft” constraints, which come with (possibly infinite) costs of particular assignments, we obtain instances from a richer class called Valued Constraint Satisfaction Problem (VCSP). There the goal is to find an assignment with minimum total cost. In this thesis, we focus (assuming that P 6 = NP) on classifying computational com- plexity of CSPs and VCSPs under certain restricting conditions. Two results are the core content of the work. In one of them, we consider VCSPs parametrized by a constraint language, that is the set of “soft” constraints allowed to form the instances, and finish the complexity classification modulo (missing pieces of) complexity classification for analogously parametrized CSP. The other result is a generalization of Edmonds’ perfect matching algorithm. This generalization contributes to complexity classfications in two ways. First, it gives a new (largest known) polynomial-time solvable class of Boolean CSPs in which every variable may appear in at most two constraints and second, it settles full classification of Boolean CSPs with planar drawing (again parametrized by a constraint language).

Expected sizes of poisson Delaunay mosaics and their discrete Morse functions - Edelsbrunner, Herbert; Nikitenko, Anton; Reitzner, Matthias (Advances in Applied Probability)
Mapping every simplex in the Delaunay mosaic of a discrete point set to the radius of the smallest empty circumsphere gives a generalized discrete Morse function. Choosing the points from a Poisson point process in ℝ n , we study the expected number of simplices in the Delaunay mosaic as well as the expected number of critical simplices and nonsingular intervals in the corresponding generalized discrete gradient. Observing connections with other probabilistic models, we obtain precise expressions for the expected numbers in low dimensions. In particular, we obtain the expected numbers of simplices in the Poisson–Delaunay mosaic in dimensions n ≤ 4.

Beyond Hellman’s time-memory trade-offs with applications to proofs of space - Abusalah, Hamza M; Alwen, Joel F; Cohen, Bram; Khilko, Danylo; Pietrzak, Krzysztof Z; Reyzin, Leonid
Proofs of space (PoS) were suggested as more ecological and economical alternative to proofs of work, which are currently used in blockchain designs like Bitcoin. The existing PoS are based on rather sophisticated graph pebbling lower bounds. Much simpler and in several aspects more efficient schemes based on inverting random functions have been suggested, but they don’t give meaningful security guarantees due to existing time-memory trade-offs. In particular, Hellman showed that any permutation over a domain of size N can be inverted in time T by an algorithm that is given S bits of auxiliary information whenever (Formula presented). For functions Hellman gives a weaker attack with S2· T≈ N2 (e.g., S= T≈ N2/3). To prove lower bounds, one considers an adversary who has access to an oracle f: [ N] → [N] and can make T oracle queries. The best known lower bound is S· T∈ Ω(N) and holds for random functions and permutations. We construct functions that provably require more time and/or space to invert. Specifically, for any constant k we construct a function [N] → [N] that cannot be inverted unless Sk· T∈ Ω(Nk) (in particular, S= T≈ (Formula presented). Our construction does not contradict Hellman’s time-memory trade-off, because it cannot be efficiently evaluated in forward direction. However, its entire function table can be computed in time quasilinear in N, which is sufficient for the PoS application. Our simplest construction is built from a random function oracle g: [N] × [N] → [ N] and a random permutation oracle f: [N] → N] and is defined as h(x) = g(x, x′) where f(x) = π(f(x′)) with π being any involution without a fixed point, e.g. flipping all the bits. For this function we prove that any adversary who gets S bits of auxiliary information, makes at most T oracle queries, and inverts h on an ϵ fraction of outputs must satisfy S2· T∈ Ω(ϵ2N2).

Singularities of the density of states of random Gram matrices - Alt, Johannes (Electronic Communications in Probability)
For large random matrices X with independent, centered entries but not necessarily identical variances, the eigenvalue density of XX* is well-approximated by a deterministic measure on ℝ. We show that the density of this measure has only square and cubic-root singularities away from zero. We also extend the bulk local law in [5] to the vicinity of these singularities.

Conic abstractions for hybrid systems - Bogomolov, Sergiy; Giacobbe, Mirco; Henzinger, Thomas A; Kong, Hui
Despite researchers’ efforts in the last couple of decades, reachability analysis is still a challenging problem even for linear hybrid systems. Among the existing approaches, the most practical ones are mainly based on bounded-time reachable set over-approximations. For the purpose of unbounded-time analysis, one important strategy is to abstract the original system and find an invariant for the abstraction. In this paper, we propose an approach to constructing a new kind of abstraction called conic abstraction for affine hybrid systems, and to computing reachable sets based on this abstraction. The essential feature of a conic abstraction is that it partitions the state space of a system into a set of convex polyhedral cones which is derived from a uniform conic partition of the derivative space. Such a set of polyhedral cones is able to cut all trajectories of the system into almost straight segments so that every segment of a reach pipe in a polyhedral cone tends to be straight as well, and hence can be over-approximated tightly by polyhedra using similar techniques as HyTech or PHAVer. In particular, for diagonalizable affine systems, our approach can guarantee to find an invariant for unbounded reachable sets, which is beyond the capability of bounded-time reachability analysis tools. We implemented the approach in a tool and experiments on benchmarks show that our approach is more powerful than SpaceEx and PHAVer in dealing with diagonalizable systems.

Counterexample guided refinement of template polyhedra - Bogomolov, Sergiy; Frehse, Goran; Giacobbe, Mirco; Henzinger, Thomas A
Template polyhedra generalize intervals and octagons to polyhedra whose facets are orthogonal to a given set of arbitrary directions. They have been employed in the abstract interpretation of programs and, with particular success, in the reachability analysis of hybrid automata. While previously, the choice of directions has been left to the user or a heuristic, we present a method for the automatic discovery of directions that generalize and eliminate spurious counterexamples. We show that for the class of convex hybrid automata, i.e., hybrid automata with (possibly nonlinear) convex constraints on derivatives, such directions always exist and can be found using convex optimization. We embed our method inside a CEGAR loop, thus enabling the time-unbounded reachability analysis of an important and richer class of hybrid automata than was previously possible. We evaluate our method on several benchmarks, demonstrating also its superior efficiency for the special case of linear hybrid automata.

Fluctuations of functions of Wigner matrices - Erdös, László; Schröder, Dominik J (Electronic Communications in Probability)
We show that matrix elements of functions of N × N Wigner matrices fluctuate on a scale of order N−1/2 and we identify the limiting fluctuation. Our result holds for any function f of the matrix that has bounded variation thus considerably relaxing the regularity requirement imposed in [7, 11].

Scattering-aware texture reproduction for 3D printing - Elek, Oskar; Sumin, Denis; Zhang, Ran; Weyrich, Tim; Myszkowski, Karol; Bickel, Bernd; Wilkie, Alexander; Krivanek, Jaroslav (ACM Transactions on Graphics)
Color texture reproduction in 3D printing commonly ignores volumetric light transport (cross-talk) between surface points on a 3D print. Such light diffusion leads to significant blur of details and color bleeding, and is particularly severe for highly translucent resin-based print materials. Given their widely varying scattering properties, this cross-talk between surface points strongly depends on the internal structure of the volume surrounding each surface point. Existing scattering-aware methods use simplified models for light diffusion, and often accept the visual blur as an immutable property of the print medium. In contrast, our work counteracts heterogeneous scattering to obtain the impression of a crisp albedo texture on top of the 3D print, by optimizing for a fully volumetric material distribution that preserves the target appearance. Our method employs an efficient numerical optimizer on top of a general Monte-Carlo simulation of heterogeneous scattering, supported by a practical calibration procedure to obtain scattering parameters from a given set of printer materials. Despite the inherent translucency of the medium, we reproduce detailed surface textures on 3D prints. We evaluate our system using a commercial, five-tone 3D print process and compare against the printer’s native color texturing mode, demonstrating that our method preserves high-frequency features well without having to compromise on color gamut.

Be adaptive avoid overcommitting - Jafargholi, Zahra; Kamath Hosdurg, Chethan; Klein, Karen; Komargodski, Ilan; Pietrzak, Krzysztof Z; Wichs, Daniel
For many cryptographic primitives, it is relatively easy to achieve selective security (where the adversary commits a-priori to some of the choices to be made later in the attack) but appears difficult to achieve the more natural notion of adaptive security (where the adversary can make all choices on the go as the attack progresses). A series of several recent works shows how to cleverly achieve adaptive security in several such scenarios including generalized selective decryption (Panjwani, TCC ’07 and Fuchsbauer et al., CRYPTO ’15), constrained PRFs (Fuchsbauer et al., ASIACRYPT ’14), and Yao garbled circuits (Jafargholi and Wichs, TCC ’16b). Although the above works expressed vague intuition that they share a common technique, the connection was never made precise. In this work we present a new framework that connects all of these works and allows us to present them in a unified and simplified fashion. Moreover, we use the framework to derive a new result for adaptively secure secret sharing over access structures defined via monotone circuits. We envision that further applications will follow in the future. Underlying our framework is the following simple idea. It is well known that selective security, where the adversary commits to n-bits of information about his future choices, automatically implies adaptive security at the cost of amplifying the adversary’s advantage by a factor of up to 2n. However, in some cases the proof of selective security proceeds via a sequence of hybrids, where each pair of adjacent hybrids locally only requires some smaller partial information consisting of m ≪ n bits. The partial information needed might be completely different between different pairs of hybrids, and if we look across all the hybrids we might rely on the entire n-bit commitment. Nevertheless, the above is sufficient to prove adaptive security, at the cost of amplifying the adversary’s advantage by a factor of only 2m ≪ 2n. In all of our examples using the above framework, the different hybrids are captured by some sort of a graph pebbling game and the amount of information that the adversary needs to commit to in each pair of hybrids is bounded by the maximum number of pebbles in play at any point in time. Therefore, coming up with better strategies for proving adaptive security translates to various pebbling strategies for different types of graphs.

Data for: Establishment in a new habitat by polygenic adaptation - Etheridge, Alison; Barton, Nicholas H
Mathematica notebooks used to generate figures.

Greedy algorithms for cone constrained optimization with convergence guarantees - Locatello, Francesco; Tschannen, Michael; Rätsch, Gunnar; Jaggi, Martin (Advances in Neural Information Processing Systems)
Greedy optimization methods such as Matching Pursuit (MP) and Frank-Wolfe (FW) algorithms regained popularity in recent years due to their simplicity, effectiveness and theoretical guarantees. MP and FW address optimization over the linear span and the convex hull of a set of atoms, respectively. In this paper, we consider the intermediate case of optimization over the convex cone, parametrized as the conic hull of a generic atom set, leading to the first principled definitions of non-negative MP algorithms for which we give explicit convergence rates and demonstrate excellent empirical performance. In particular, we derive sublinear (O(1/t)) convergence on general smooth and convex objectives, and linear convergence (O(e−t)) on strongly convex objectives, in both cases for general sets of atoms. Furthermore, we establish a clear correspondence of our algorithms to known algorithms from the MP and FW literature. Our novel algorithms and analyses target general atom sets and general objective functions, and hence are directly applicable to a large variety of learning settings.

A unified optimization view on generalized matching pursuit and Frank-Wolfe - Locatello, Francesco; Khanna, Rajiv; Tschannen, Michael; Jaggi, Martin (Proceedings of the 20th International Conference on Artificial Intelligence and Statistics)
Two of the most fundamental prototypes of greedy optimization are the matching pursuit and Frank-Wolfe algorithms. In this paper, we take a unified view on both classes of methods, leading to the first explicit convergence rates of matching pursuit methods in an optimization sense, for general sets of atoms. We derive sublinear (1/t) convergence for both classes on general smooth objectives, and linear convergence on strongly convex objectives, as well as a clear correspondence of algorithm variants. Our presented algorithms and rates are affine invariant, and do not need any incoherence or sparsity assumptions.

Biology of restriction-modification systems at the single-cell and population level - Pleska, Maros
Restriction-modification (RM) represents the simplest and possibly the most widespread mechanism of self/non-self discrimination in nature. In order to provide bacteria with immunity against bacteriophages and other parasitic genetic elements, RM systems rely on a balance between two enzymes: the restriction enzyme, which cleaves non-self DNA at specific restriction sites, and the modification enzyme, which tags the host’s DNA as self and thus protects it from cleavage. In this thesis, I use population and single-cell level experiments in combination with mathematical modeling to study different aspects of the interplay between RM systems, bacteria and bacteriophages. First, I analyze how mutations in phage restriction sites affect the probability of phage escape – an inherently stochastic process, during which phages accidently get modified instead of restricted. Next, I use single-cell experiments to show that RM systems can, with a low probability, attack the genome of their bacterial host and that this primitive form of autoimmunity leads to a tradeoff between the evolutionary cost and benefit of RM systems. Finally, I investigate the nature of interactions between bacteria, RM systems and temperate bacteriophages to find that, as a consequence of phage escape and its impact on population dynamics, RM systems can promote acquisition of symbiotic bacteriophages, rather than limit it. The results presented here uncover new fundamental biological properties of RM systems and highlight their importance in the ecology and evolution of bacteria, bacteriophages and their interactions.

Discrete Morse theory for random complexes - Nikitenko, Anton
The main objects considered in the present work are simplicial and CW-complexes with vertices forming a random point cloud. In particular, we consider a Poisson point process in R^n and study Delaunay and Voronoi complexes of the first and higher orders and weighted Delaunay complexes obtained as sections of Delaunay complexes, as well as the Čech complex. Further, we examine theDelaunay complex of a Poisson point process on the sphere S^n, as well as of a uniform point cloud, which is equivalent to the convex hull, providing a connection to the theory of random polytopes. Each of the complexes in question can be endowed with a radius function, which maps its cells to the radii of appropriately chosen circumspheres, called the radius of the cell. Applying and developing discrete Morse theory for these functions, joining it together with probabilistic and sometimes analytic machinery, and developing several integral geometric tools, we aim at getting the distributions of circumradii of typical cells. For all considered complexes, we are able to generalize and obtain up to constants the distribution of radii of typical intervals of all types. In low dimensions the constants can be computed explicitly, thus providing the explicit expressions for the expected numbers of cells. In particular, it allows to find the expected density of simplices of every dimension for a Poisson point process in R^4, whereas the result for R^3 was known already in 1970's.

Identification of novel regulators of PIN polarity and development of novel auxin sensor - Prat, Tomas
Plant hormone auxin and its transport between cells belong to the most important mechanisms controlling plant development. Auxin itself could change localization of PINs and thereby control direction of its own flow. We performed an expression profiling experiment in Arabidopsis roots to identify potential regulators of PIN polarity which are transcriptionally regulated by auxin signalling. We identified several novel regulators and performed a detailed characterization of the transcription factor WRKY23 (At2g47260) and its role in auxin feedback on PIN polarity. Gain-of-function and dominant-negative mutants revealed that WRKY23 plays a crucial role in mediating the auxin effect on PIN polarity. In concordance, typical polar auxin transport processes such as gravitropism and leaf vascular pattern formation were disturbed by interfering with WRKY23 function. In order to identify direct targets of WRKY23, we performed consequential expression profiling experiments using a WRKY23 inducible gain-of-function line and dominant-negative WRKY23 line that is defunct in PIN re-arrangement. Among several genes mostly related to the groups of cell wall and defense process regulators, we identified LYSINE-HISTIDINE TRANSPORTER 1 (LHT1; At5g40780), a small amino acid permease gene from the amino acid/auxin permease family (AAAP), we present its detailed characterisation in auxin feedback on PIN repolarization, identified its transcriptional regulation, we propose a potential mechanism of its action. Moreover, we identified also a member of receptor-like protein kinase LRR-RLK (LEUCINE-RICH REPEAT TRANSMEMBRANE PROTEIN KINASE PROTEIN 1; LRRK1; At1g05700), which also affects auxin-dependent PIN re-arrangement. We described its transcriptional behaviour, subcellular localization. Based on global expression data, we tried to identify ligand responsible for mechanism of signalling and suggest signalling partner and interactors. Additionally, we described role of novel phytohormone group, strigolactone, in auxin-dependent PIN re-arrangement, that could be a fundament for future studies in this field. Our results provide first insights into an auxin transcriptional network targeting PIN localization and thus regulating plant development. We highlighted WRKY23 transcriptional network and characterised its mediatory role in plant development. We identified direct effectors of this network, LHT1 and LRRK1, and describe their roles in PIN re-arrangement and PIN-dependent auxin transport processes.

Exact goodness-of-fit testing for the Ising model - Martin Del Campo Sanchez, Abraham; Cepeda Humerez, Sarah A; Uhler, Caroline (Scandinavian Journal of Statistics)
The Ising model is one of the simplest and most famous models of interacting systems. It was originally proposed to model ferromagnetic interactions in statistical physics and is now widely used to model spatial processes in many areas such as ecology, sociology, and genetics, usually without testing its goodness-of-fit. Here, we propose an exact goodness-of-fit test for the finite-lattice Ising model. The theory of Markov bases has been developed in algebraic statistics for exact goodness-of-fit testing using a Monte Carlo approach. However, this beautiful theory has fallen short of its promise for applications, because finding a Markov basis is usually computationally intractable. We develop a Monte Carlo method for exact goodness-of-fit testing for the Ising model which avoids computing a Markov basis and also leads to a better connectivity of the Markov chain and hence to a faster convergence. We show how this method can be applied to analyze the spatial organization of receptors on the cell membrane.

Delocalization for a class of random block band matrices - Bao, Zhigang; Erdös, László (Probability Theory and Related Fields)
We consider N×N Hermitian random matrices H consisting of blocks of size M≥N6/7. The matrix elements are i.i.d. within the blocks, close to a Gaussian in the four moment matching sense, but their distribution varies from block to block to form a block-band structure, with an essential band width M. We show that the entries of the Green’s function G(z)=(H−z)−1 satisfy the local semicircle law with spectral parameter z=E+iη down to the real axis for any η≫N−1, using a combination of the supersymmetry method inspired by Shcherbina (J Stat Phys 155(3): 466–499, 2014) and the Green’s function comparison strategy. Previous estimates were valid only for η≫M−1. The new estimate also implies that the eigenvectors in the middle of the spectrum are fully delocalized.

Phat - Persistent homology algorithms toolbox - Bauer, Ulrich; Kerber, Michael; Reininghaus, Jan; Wagner, Hubert (Journal of Symbolic Computation)
Phat is an open-source C. ++ library for the computation of persistent homology by matrix reduction, targeted towards developers of software for topological data analysis. We aim for a simple generic design that decouples algorithms from data structures without sacrificing efficiency or user-friendliness. We provide numerous different reduction strategies as well as data types to store and manipulate the boundary matrix. We compare the different combinations through extensive experimental evaluation and identify optimization techniques that work well in practical situations. We also compare our software with various other publicly available libraries for persistent homology.

Temporal logic control for stochastic linear systems using abstraction refinement of probabilistic games - Svoreňová, Mária; Kretinsky, Jan; Chmelik, Martin; Chatterjee, Krishnendu; Cěrná, Ivana; Belta, Cǎlin (Nonlinear Analysis: Hybrid Systems)
We consider the problem of computing the set of initial states of a dynamical system such that there exists a control strategy to ensure that the trajectories satisfy a temporal logic specification with probability 1 (almost-surely). We focus on discrete-time, stochastic linear dynamics and specifications given as formulas of the Generalized Reactivity(1) fragment of Linear Temporal Logic over linear predicates in the states of the system. We propose a solution based on iterative abstraction-refinement, and turn-based 2-player probabilistic games. While the theoretical guarantee of our algorithm after any finite number of iterations is only a partial solution, we show that if our algorithm terminates, then the result is the set of all satisfying initial states. Moreover, for any (partial) solution our algorithm synthesizes witness control strategies to ensure almost-sure satisfaction of the temporal logic specification. While the proposed algorithm guarantees progress and soundness in every iteration, it is computationally demanding. We offer an alternative, more efficient solution for the reachability properties that decomposes the problem into a series of smaller problems of the same type. All algorithms are demonstrated on an illustrative case study.

Adaptive physically based models in computer graphics - Manteaux, Pierre; Wojtan, Christopher J; Narain, Rahul; Redon, Stéphane; Faure, François; Cani, Marie (Computer Graphics Forum)
One of the major challenges in physically based modelling is making simulations efficient. Adaptive models provide an essential solution to these efficiency goals. These models are able to self-adapt in space and time, attempting to provide the best possible compromise between accuracy and speed. This survey reviews the adaptive solutions proposed so far in computer graphics. Models are classified according to the strategy they use for adaptation, from time-stepping and freezing techniques to geometric adaptivity in the form of structured grids, meshes and particles. Applications range from fluids, through deformable bodies, to articulated solids.

From non-preemptive to preemptive scheduling using synchronization synthesis - Cerny, Pavol; Clarke, Edmund; Henzinger, Thomas A; Radhakrishna, Arjun; Ryzhyk, Leonid; Samanta, Roopsha; Tarrach, Thorsten (Formal Methods in System Design)
We present a computer-aided programming approach to concurrency. The approach allows programmers to program assuming a friendly, non-preemptive scheduler, and our synthesis procedure inserts synchronization to ensure that the final program works even with a preemptive scheduler. The correctness specification is implicit, inferred from the non-preemptive behavior. Let us consider sequences of calls that the program makes to an external interface. The specification requires that any such sequence produced under a preemptive scheduler should be included in the set of sequences produced under a non-preemptive scheduler. We guarantee that our synthesis does not introduce deadlocks and that the synchronization inserted is optimal w.r.t. a given objective function. The solution is based on a finitary abstraction, an algorithm for bounded language inclusion modulo an independence relation, and generation of a set of global constraints over synchronization placements. Each model of the global constraints set corresponds to a correctness-ensuring synchronization placement. The placement that is optimal w.r.t. the given objective function is chosen as the synchronization solution. We apply the approach to device-driver programming, where the driver threads call the software interface of the device and the API provided by the operating system. Our experiments demonstrate that our synthesis method is precise and efficient. The implicit specification helped us find one concurrency bug previously missed when model-checking using an explicit, user-provided specification. We implemented objective functions for coarse-grained and fine-grained locking and observed that different synchronization placements are produced for our experiments, favoring a minimal number of synchronization operations or maximum concurrency, respectively.

Model checking the evolution of gene regulatory networks - Giacobbe, Mirco; Guet, Calin C; Gupta, Ashutosh; Henzinger, Thomas A; Paixao, Tiago; Petrov, Tatjana (Acta Informatica)
The behaviour of gene regulatory networks (GRNs) is typically analysed using simulation-based statistical testing-like methods. In this paper, we demonstrate that we can replace this approach by a formal verification-like method that gives higher assurance and scalability. We focus on Wagner’s weighted GRN model with varying weights, which is used in evolutionary biology. In the model, weight parameters represent the gene interaction strength that may change due to genetic mutations. For a property of interest, we synthesise the constraints over the parameter space that represent the set of GRNs satisfying the property. We experimentally show that our parameter synthesis procedure computes the mutational robustness of GRNs—an important problem of interest in evolutionary biology—more efficiently than the classical simulation method. We specify the property in linear temporal logic. We employ symbolic bounded model checking and SMT solving to compute the space of GRNs that satisfy the property, which amounts to synthesizing a set of linear constraints on the weights.

Towards a runtime comparison of natural and artificial evolution - Paixao, Tiago; Pérez Heredia, Jorge; Sudholt, Dirk; Trubenova, Barbora (Algorithmica)
Evolutionary algorithms (EAs) form a popular optimisation paradigm inspired by natural evolution. In recent years the field of evolutionary computation has developed a rigorous analytical theory to analyse the runtimes of EAs on many illustrative problems. Here we apply this theory to a simple model of natural evolution. In the Strong Selection Weak Mutation (SSWM) evolutionary regime the time between occurrences of new mutations is much longer than the time it takes for a mutated genotype to take over the population. In this situation, the population only contains copies of one genotype and evolution can be modelled as a stochastic process evolving one genotype by means of mutation and selection between the resident and the mutated genotype. The probability of accepting the mutated genotype then depends on the change in fitness. We study this process, SSWM, from an algorithmic perspective, quantifying its expected optimisation time for various parameters and investigating differences to a similar evolutionary algorithm, the well-known (1+1) EA. We show that SSWM can have a moderate advantage over the (1+1) EA at crossing fitness valleys and study an example where SSWM outperforms the (1+1) EA by taking advantage of information on the fitness gradient.

Universality for general Wigner-type matrices - Ajanki, Oskari H; Erdös, László; Krüger, Torben H (Probability Theory and Related Fields)
We consider the local eigenvalue distribution of large self-adjoint N×N random matrices H=H∗ with centered independent entries. In contrast to previous works the matrix of variances sij=\mathbbmE|hij|2 is not assumed to be stochastic. Hence the density of states is not the Wigner semicircle law. Its possible shapes are described in the companion paper (Ajanki et al. in Quadratic Vector Equations on the Complex Upper Half Plane. arXiv:1506.05095). We show that as N grows, the resolvent, G(z)=(H−z)−1, converges to a diagonal matrix, diag(m(z)), where m(z)=(m1(z),…,mN(z)) solves the vector equation −1/mi(z)=z+∑jsijmj(z) that has been analyzed in Ajanki et al. (Quadratic Vector Equations on the Complex Upper Half Plane. arXiv:1506.05095). We prove a local law down to the smallest spectral resolution scale, and bulk universality for both real symmetric and complex hermitian symmetry classes.

Trading performance for stability in Markov decision processes - Brázdil, Tomáš; Chatterjee, Krishnendu; Forejt, Vojtěch; Kučera, Antonín (Journal of Computer and System Sciences)
We study controller synthesis problems for finite-state Markov decision processes, where the objective is to optimize the expected mean-payoff performance and stability (also known as variability in the literature). We argue that the basic notion of expressing the stability using the statistical variance of the mean payoff is sometimes insufficient, and propose an alternative definition. We show that a strategy ensuring both the expected mean payoff and the variance below given bounds requires randomization and memory, under both the above definitions. We then show that the problem of finding such a strategy can be expressed as a set of constraints.

Are reprogrammed cells a useful tool for studying dopamine dysfunction in psychotic disorders? A review of the current evidence - Sauerzopf, Ulrich; Sacco, Roberto; Novarino, Gaia; Niello, Marco; Weidenauer, Ana; Praschak Rieder, Nicole; Sitte, Harald; Willeit, Matthaeus (European Journal of Neuroscience)
Since 2006, reprogrammed cells have increasingly been used as a biomedical research technique in addition to neuro-psychiatric methods. These rapidly evolving techniques allow for the generation of neuronal sub-populations, and have sparked interest not only in monogenetic neuro-psychiatric diseases, but also in poly-genetic and poly-aetiological disorders such as schizophrenia (SCZ) and bipolar disorder (BPD). This review provides a summary of 19 publications on reprogrammed adult somatic cells derived from patients with SCZ, and five publications using this technique in patients with BPD. As both disorders are complex and heterogeneous, there is a plurality of hypotheses to be tested in vitro. In SCZ, data on alterations of dopaminergic transmission in vitro are sparse, despite the great explanatory power of the so-called DA hypothesis of SCZ. Some findings correspond to perturbations of cell energy metabolism, and observations in reprogrammed cells suggest neuro-developmental alterations. Some studies also report on the efficacy of medicinal compounds to revert alterations observed in cellular models. However, due to the paucity of replication studies, no comprehensive conclusions can be drawn from studies using reprogrammed cells at the present time. In the future, findings from cell culture methods need to be integrated with clinical, epidemiological, pharmacological and imaging data in order to generate a more comprehensive picture of SCZ and BPD.

Single-molecule measurements to study polymerization dynamics of FtsZ-FtsA copolymers - Baranova, Natalia; Loose, Martin (Cytokinesis)
Bacterial cytokinesis is commonly initiated by the Z-ring, a dynamic cytoskeletal structure that assembles at the site of division. Its primary component is FtsZ, a tubulin-like GTPase, that like its eukaryotic relative forms protein filaments in the presence of GTP. Since the discovery of the Z-ring 25 years ago, various models for the role of FtsZ have been suggested. However, important information about the architecture and dynamics of FtsZ filaments during cytokinesis is still missing. One reason for this lack of knowledge has been the small size of bacteria, which has made it difficult to resolve the orientation and dynamics of individual FtsZ filaments in the Z-ring. While superresolution microscopy experiments have helped to gain more information about the organization of the Z-ring in the dividing cell, they were not yet able to elucidate a mechanism of how FtsZ filaments reorganize during assembly and disassembly of the Z-ring. In this chapter, we explain how to use an in vitro reconstitution approach to investigate the self-organization of FtsZ filaments recruited to a biomimetic lipid bilayer by its membrane anchor FtsA. We show how to perform single-molecule experiments to study the behavior of individual FtsZ monomers during the constant reorganization of the FtsZ-FtsA filament network. We describe how to analyze the dynamics of single molecules and explain why this information can help to shed light onto possible mechanism of Z-ring constriction. We believe that similar experimental approaches will be useful to study the mechanism of membrane-based polymerization of other cytoskeletal systems, not only from prokaryotic but also eukaryotic origin.

Triviality of a model of particles with point interactions in the thermodynamic limit - Moser, Thomas; Seiringer, Robert (Letters in Mathematical Physics)
We consider a model of fermions interacting via point interactions, defined via a certain weighted Dirichlet form. While for two particles the interaction corresponds to infinite scattering length, the presence of further particles effectively decreases the interaction strength. We show that the model becomes trivial in the thermodynamic limit, in the sense that the free energy density at any given particle density and temperature agrees with the corresponding expression for non-interacting particles.

Local law of addition of random matrices on optimal scale - Bao, Zhigang; Erdös, László; Schnelli, Kevin (Communications in Mathematical Physics)
The eigenvalue distribution of the sum of two large Hermitian matrices, when one of them is conjugated by a Haar distributed unitary matrix, is asymptotically given by the free convolution of their spectral distributions. We prove that this convergence also holds locally in the bulk of the spectrum, down to the optimal scales larger than the eigenvalue spacing. The corresponding eigenvectors are fully delocalized. Similar results hold for the sum of two real symmetric matrices, when one is conjugated by Haar orthogonal matrix.

Model measuring for discrete and hybrid systems - Henzinger, Thomas A; Otop, Jan (Nonlinear Analysis: Hybrid Systems)
We define the . model-measuring problem: given a model . M and specification . ϕ, what is the maximal distance . ρ such that all models . M' within distance . ρ from . M satisfy (or violate) . ϕ. The model-measuring problem presupposes a distance function on models. We concentrate on . automatic distance functions, which are defined by weighted automata. The model-measuring problem subsumes several generalizations of the classical model-checking problem, in particular, quantitative model-checking problems that measure the degree of satisfaction of a specification; robustness problems that measure how much a model can be perturbed without violating the specification; and parameter synthesis for hybrid systems. We show that for automatic distance functions, and (a) . ω-regular linear-time, (b) . ω-regular branching-time, and (c) hybrid specifications, the model-measuring problem can be solved.We use automata-theoretic model-checking methods for model measuring, replacing the emptiness question for word, tree, and hybrid automata by the . optimal-value question for the weighted versions of these automata. For automata over words and trees, we consider weighted automata that accumulate weights by maximizing, summing, discounting, and limit averaging. For hybrid automata, we consider monotonic (parametric) hybrid automata, a hybrid counterpart of (discrete) weighted automata.We give several examples of using the model-measuring problem to compute various notions of robustness and quantitative satisfaction for temporal specifications. Further, we propose the modeling framework for model measuring to ease the specification and reduce the likelihood of errors in modeling.Finally, we present a variant of the model-measuring problem, called the . model-repair problem. The model-repair problem applies to models that do not satisfy the specification; it can be used to derive restrictions, under which the model satisfies the specification, i.e., to repair the model.

How does epistasis influence the response to selection? - Barton, Nicholas H (Heredity)
Much of quantitative genetics is based on the ‘infinitesimal model’, under which selection has a negligible effect on the genetic variance. This is typically justified by assuming a very large number of loci with additive effects. However, it applies even when genes interact, provided that the number of loci is large enough that selection on each of them is weak relative to random drift. In the long term, directional selection will change allele frequencies, but even then, the effects of epistasis on the ultimate change in trait mean due to selection may be modest. Stabilising selection can maintain many traits close to their optima, even when the underlying alleles are weakly selected. However, the number of traits that can be optimised is apparently limited to ~4Ne by the ‘drift load’, and this is hard to reconcile with the apparent complexity of many organisms. Just as for the mutation load, this limit can be evaded by a particular form of negative epistasis. A more robust limit is set by the variance in reproductive success. This suggests that selection accumulates information most efficiently in the infinitesimal regime, when selection on individual alleles is weak, and comparable with random drift. A review of evidence on selection strength suggests that although most variance in fitness may be because of alleles with large Nes, substantial amounts of adaptation may be because of alleles in the infinitesimal regime, in which epistasis has modest effects.

Maximum likelihood estimation for linear Gaussian covariance models - Zwiernik, Piotr; Uhler, Caroline; Richards, Donald (Journal of the Royal Statistical Society. Series B: Statistical Methodology)
We study parameter estimation in linear Gaussian covariance models, which are p-dimensional Gaussian models with linear constraints on the covariance matrix. Maximum likelihood estimation for this class of models leads to a non-convex optimization problem which typically has many local maxima. Using recent results on the asymptotic distribution of extreme eigenvalues of the Wishart distribution, we provide sufficient conditions for any hill climbing method to converge to the global maximum. Although we are primarily interested in the case in which n≫p, the proofs of our results utilize large sample asymptotic theory under the scheme n/p→γ>1. Remarkably, our numerical simulations indicate that our results remain valid for p as small as 2. An important consequence of this analysis is that, for sample sizes n≃14p, maximum likelihood estimation for linear Gaussian covariance models behaves as if it were a convex optimization problem. © 2016 The Royal Statistical Society and Blackwell Publishing Ltd.

Lower bounds on key derivation for square-friendly applications - Skórski, Maciej
Security of cryptographic applications is typically defined by security games. The adversary, within certain resources, cannot win with probability much better than 0 (for unpredictability applications, like one-way functions) or much better than 1/2 (indistinguishability applications for instance encryption schemes). In so called squared-friendly applications the winning probability of the adversary, for different values of the application secret randomness, is not only close to 0 or 1/2 on average, but also concentrated in the sense that its second central moment is small. The class of squared-friendly applications, which contains all unpredictability applications and many indistinguishability applications, is particularly important for key derivation. Barak et al. observed that for square-friendly applications one can beat the "RT-bound", extracting secure keys with significantly smaller entropy loss. In turn Dodis and Yu showed that in squared-friendly applications one can directly use a "weak" key, which has only high entropy, as a secure key. In this paper we give sharp lower bounds on square security assuming security for "weak" keys. We show that any application which is either (a) secure with weak keys or (b) allows for entropy savings for keys derived by universal hashing, must be square-friendly. Quantitatively, our lower bounds match the positive results of Dodis and Yu and Barak et al. (TCC\'13, CRYPTO\'11) Hence, they can be understood as a general characterization of squared-friendly applications. While the positive results on squared-friendly applications where derived by one clever application of the Cauchy-Schwarz Inequality, for tight lower bounds we need more machinery. In our approach we use convex optimization techniques and some theory of circular matrices.

Towards practical attacks on Argon2i and balloon hashing - Alwen, Joel F; Blocki, Jeremiah
The algorithm Argon2i-B of Biryukov, Dinu and Khovratovich is currently being considered by the IRTF (Internet Research Task Force) as a new de-facto standard for password hashing. An older version (Argon2i-A) of the same algorithm was chosen as the winner of the recent Password Hashing Competition. An important competitor to Argon2i-B is the recently introduced Balloon Hashing (BH) algorithm of Corrigan-Gibs, Boneh and Schechter. A key security desiderata for any such algorithm is that evaluating it (even using a custom device) requires a large amount of memory amortized across multiple instances. Alwen and Blocki (CRYPTO 2016) introduced a class of theoretical attacks against Argon2i-A and BH. While these attacks yield large asymptotic reductions in the amount of memory, it was not, a priori, clear if (1) they can be extended to the newer Argon2i-B, (2) the attacks are effective on any algorithm for practical parameter ranges (e.g., 1GB of memory) and (3) if they can be effectively instantiated against any algorithm under realistic hardware constrains. In this work we answer all three of these questions in the affirmative for all three algorithms. This is also the first work to analyze the security of Argon2i-B. In more detail, we extend the theoretical attacks of Alwen and Blocki (CRYPTO 2016) to the recent Argon2i-B proposal demonstrating severe asymptotic deficiencies in its security. Next we introduce several novel heuristics for improving the attack's concrete memory efficiency even when on-chip memory bandwidth is bounded. We then simulate our attacks on randomly sampled Argon2i-A, Argon2i-B and BH instances and measure the resulting memory consumption for various practical parameter ranges and for a variety of upperbounds on the amount of parallelism available to the attacker. Finally we describe, implement, and test a new heuristic for applying the Alwen-Blocki attack to functions employing a technique developed by Corrigan-Gibs et al. for improving concrete security of memory-hard functions. We analyze the collected data and show the effects various parameters have on the memory consumption of the attack. In particular, we can draw several interesting conclusions about the level of security provided by these functions. · For the Alwen-Blocki attack to fail against practical memory parameters, Argon2i-B must be instantiated with more than 10 passes on memory - beyond the "paranoid" parameter setting in the current IRTF proposal. · The technique of Corrigan-Gibs for improving security can also be overcome by the Alwen-Blocki attack under realistic hardware constraints. · On a positive note, both the asymptotic and concrete security of Argon2i-B seem to improve on that of Argon2i-A.

Efficient authentication from hard learning problems - Kiltz, Eike; Pietrzak, Krzysztof Z; Venturi, Daniele; Cash, David; Jain, Abhishek (Journal of Cryptology)
We construct efficient authentication protocols and message authentication codes (MACs) whose security can be reduced to the learning parity with noise (LPN) problem. Despite a large body of work—starting with the (Formula presented.) protocol of Hopper and Blum in 2001—until now it was not even known how to construct an efficient authentication protocol from LPN which is secure against man-in-the-middle attacks. A MAC implies such a (two-round) protocol.

Even delta-matroids and the complexity of planar Boolean CSPs - Kazda, Alexandr; Kolmogorov, Vladimir; Rolinek, Michal
The main result of this paper is a generalization of the classical blossom algorithm for finding perfect matchings. Our algorithm can efficiently solve Boolean CSPs where each variable appears in exactly two constraints (we call it edge CSP) and all constraints are even Δ-matroid relations (represented by lists of tuples). As a consequence of this, we settle the complexity classification of planar Boolean CSPs started by Dvorak and Kupec. Knowing that edge CSP is tractable for even Δ-matroid constraints allows us to extend the tractability result to a larger class of Δ-matroids that includes many classes that were known to be tractable before, namely co-independent, compact, local and binary.

Algebraic vertices of non-convex polyhedra - Akopyan, Arseniy; Bárány, Imre; Robins, Sinai (Advances in Mathematics)
In this article we define an algebraic vertex of a generalized polyhedron and show that the set of algebraic vertices is the smallest set of points needed to define the polyhedron. We prove that the indicator function of a generalized polytope P is a linear combination of indicator functions of simplices whose vertices are algebraic vertices of P. We also show that the indicator function of any generalized polyhedron is a linear combination, with integer coefficients, of indicator functions of cones with apices at algebraic vertices and line-cones. The concept of an algebraic vertex is closely related to the Fourier–Laplace transform. We show that a point v is an algebraic vertex of a generalized polyhedron P if and only if the tangent cone of P, at v, has non-zero Fourier–Laplace transform.

Cis-cinnamic acid is a novel natural auxin efflux inhibitor that promotes lateral root formation - Steenackers, Ward; Klíma, Petr; Quareshy, Mussa; Cesarino, Igor; Kumpf, Robert; Corneillie, Sander; Araújo, Pedro; Viaene, Tom; Goeminne, Geert; Nowack, Moritz; Ljung, Karin; Friml, Jirí; et al. (Plant Physiology)
Auxin steers numerous physiological processes in plants, making the tight control of its endogenous levels and spatiotemporal distribution a necessity. This regulation is achieved by different mechanisms, including auxin biosynthesis, metabolic conversions, degradation, and transport. Here, we introduce cis-cinnamic acid (c-CA) as a novel and unique addition to a small group of endogenous molecules affecting in planta auxin concentrations. c-CA is the photo-isomerization product of the phenylpropanoid pathway intermediate trans-CA (t-CA). When grown on c-CA-containing medium, an evolutionary diverse set of plant species were shown to exhibit phenotypes characteristic for high auxin levels, including inhibition of primary root growth, induction of root hairs, and promotion of adventitious and lateral rooting. By molecular docking and receptor binding assays, we showed that c-CA itself is neither an auxin nor an anti-auxin, and auxin profiling data revealed that c-CA does not significantly interfere with auxin biosynthesis. Single cell-based auxin accumulation assays showed that c-CA, and not t-CA, is a potent inhibitor of auxin efflux. Auxin signaling reporters detected changes in spatiotemporal distribution of the auxin response along the root of c-CA-treated plants, and long-distance auxin transport assays showed no inhibition of rootward auxin transport. Overall, these results suggest that the phenotypes of c-CA-treated plants are the consequence of a local change in auxin accumulation, induced by the inhibition of auxin efflux. This work reveals a novel mechanism how plants may regulate auxin levels and adds a novel, naturally occurring molecule to the chemical toolbox for the studies of auxin homeostasis.

Spatial gene frequency waves under genotype dependent dispersal - Novak, Sebastian; Kollár, Richard (Genetics)
Dispersal is a crucial factor in natural evolution, since it determines the habitat experienced by any population and defines the spatial scale of interactions between individuals. There is compelling evidence for systematic differences in dispersal characteristics within the same population, i.e., genotype-dependent dispersal. The consequences of genotype-dependent dispersal on other evolutionary phenomena, however, are poorly understood. In this article we investigate the effect of genotype-dependent dispersal on spatial gene frequency patterns, using a generalization of the classical diffusion model of selection and dispersal. Dispersal is characterized by the variance of dispersal (diffusion coefficient) and the mean displacement (directional advection term). We demonstrate that genotype-dependent dispersal may change the qualitative behavior of Fisher waves, which change from being “pulled” to being “pushed” wave fronts as the discrepancy in dispersal between genotypes increases. The speed of any wave is partitioned into components due to selection, genotype-dependent variance of dispersal, and genotype-dependent mean displacement. We apply our findings to wave fronts maintained by selection against heterozygotes. Furthermore, we identify a benefit of increased variance of dispersal, quantify its effect on the speed of the wave, and discuss the implications for the evolution of dispersal strategies.

Dynamics of ferrofluidic flow in the Taylor-Couette system with a small aspect ratio - Altmeyer, Sebastian; Do, Younghae; Lai, Ying (Scientific Reports)
We investigate fundamental nonlinear dynamics of ferrofluidic Taylor-Couette flow - flow confined be-tween two concentric independently rotating cylinders - consider small aspect ratio by solving the ferro-hydrodynamical equations, carrying out systematic bifurcation analysis. Without magnetic field, we find steady flow patterns, previously observed with a simple fluid, such as those containing normal one- or two vortex cells, as well as anomalous one-cell and twin-cell flow states. However, when a symmetry-breaking transverse magnetic field is present, all flow states exhibit stimulated, finite two-fold mode. Various bifurcations between steady and unsteady states can occur, corresponding to the transitions between the two-cell and one-cell states. While unsteady, axially oscillating flow states can arise, we also detect the emergence of new unsteady flow states. In particular, we uncover two new states: one contains only the azimuthally oscillating solution in the configuration of the twin-cell flow state, and an-other a rotating flow state. Topologically, these flow states are a limit cycle and a quasiperiodic solution on a two-torus, respectively. Emergence of new flow states in addition to observed ones with classical fluid, indicates that richer but potentially more controllable dynamics in ferrofluidic flows, as such flow states depend on the external magnetic field.

Universal properties of high temperature superconductors from real space pairing t-J-U model and its quantitative comparison with experiment - Spałek, Jozef; Zegrodnik, Michał; Kaczmarczyk, Jan (Physical Review B - Condensed Matter and Materials Physics)
Selected universal experimental properties of high-temperature superconducting (HTS) cuprates have been singled out in the last decade. One of the pivotal challenges in this field is the designation of a consistent interpretation framework within which we can describe quantitatively the universal features of those systems. Here we analyze in a detailed manner the principal experimental data and compare them quantitatively with the approach based on a single-band model of strongly correlated electrons supplemented with strong antiferromagnetic (super)exchange interaction (the so-called t−J−U model). The model rationale is provided by estimating its microscopic parameters on the basis of the three-band approach for the Cu-O plane. We use our original full Gutzwiller wave-function solution by going beyond the renormalized mean-field theory (RMFT) in a systematic manner. Our approach reproduces very well the observed hole doping (δ) dependence of the kinetic-energy gain in the superconducting phase, one of the principal non-Bardeen-Cooper-Schrieffer features of the cuprates. The calculated Fermi velocity in the nodal direction is practically δ-independent and its universal value agrees very well with that determined experimentally. Also, a weak doping dependence of the Fermi wave vector leads to an almost constant value of the effective mass in a pure superconducting phase which is both observed in experiment and reproduced within our approach. An assessment of the currently used models (t−J, Hubbard) is carried out and the results of the canonical RMFT as a zeroth-order solution are provided for comparison to illustrate the necessity of the introduced higher-order contributions.

A multi objective memetic inverse solver reinforced by local optimization methods - Gajda-Zagorska, Ewa P; Schaefer, Robert; Smołka, Maciej; Pardo, David; Alvarez Aramberri, Julen (Journal of Computational Science)
We propose a new memetic strategy that can solve the multi-physics, complex inverse problems, formulated as the multi-objective optimization ones, in which objectives are misfits between the measured and simulated states of various governing processes. The multi-deme structure of the strategy allows for both, intensive, relatively cheap exploration with a moderate accuracy and more accurate search many regions of Pareto set in parallel. The special type of selection operator prefers the coherent alternative solutions, eliminating artifacts appearing in the particular processes. The additional accuracy increment is obtained by the parallel convex searches applied to the local scalarizations of the misfit vector. The strategy is dedicated for solving ill-conditioned problems, for which inverting the single physical process can lead to the ambiguous results. The skill of the selection in artifact elimination is shown on the benchmark problem, while the whole strategy was applied for identification of oil deposits, where the misfits are related to various frequencies of the magnetic and electric waves of the magnetotelluric measurements. 2016 Elsevier B.V.

D inf s optimality in copula models - Perrone, Elisa; Rappold, Andreas; Müller, Werner (Statistical Methods and Applications)
Optimum experimental design theory has recently been extended for parameter estimation in copula models. The use of these models allows one to gain in flexibility by considering the model parameter set split into marginal and dependence parameters. However, this separation also leads to the natural issue of estimating only a subset of all model parameters. In this work, we treat this problem with the application of the (Formula presented.)-optimality to copula models. First, we provide an extension of the corresponding equivalence theory. Then, we analyze a wide range of flexible copula models to highlight the usefulness of (Formula presented.)-optimality in many possible scenarios. Finally, we discuss how the usage of the introduced design criterion also relates to the more general issue of copula selection and optimal design for model discrimination.

Unconventional superconductivity in generalized Hubbard model role of electron–hole symmetry breaking terms - Wysokiński, Marcin; Kaczmarczyk, Jan (Journal of Physics: Condensed Matter)
We investigate the effect of the electron-hole (e-h) symmetry breaking on d-wave superconductivity induced by non-local effects of correlations in the generalized Hubbard model. The symmetry breaking is introduced in a two-fold manner: by the next-to-nearest neighbor hopping of electrons and by the charge-bond interaction - the off-diagonal term of the Coulomb potential. Both terms lead to a pronounced asymmetry of the superconducting order parameter. The next-to-nearest neighbor hopping enhances superconductivity for h-doping, while diminishes it for e-doping. The charge-bond interaction alone leads to the opposite effect and, additionally, to the kinetic-energy gain upon condensation in the underdoped regime. With both terms included, with similar amplitudes, the height of the superconducting dome and the critical doping remain in favor of h-doping. The influence of the charge-bond interaction on deviations from symmetry of the shape of the gap at the Fermi surface in the momentum space is briefly discussed.

The Voronoi functional is maximized by the Delaunay triangulation in the plane - Edelsbrunner, Herbert; Glazyrin, Alexey; Musin, Oleg; Nikitenko, Anton (Combinatorica)
We introduce the Voronoi functional of a triangulation of a finite set of points in the Euclidean plane and prove that among all geometric triangulations of the point set, the Delaunay triangulation maximizes the functional. This result neither extends to topological triangulations in the plane nor to geometric triangulations in three and higher dimensions.

Cell migration: Making the waves - Müller, Jan; Sixt, Michael K (Current Biology)
Coordinated changes of cell shape are often the result of the excitable, wave-like dynamics of the actin cytoskeleton. New work shows that, in migrating cells, protrusion waves arise from mechanochemical crosstalk between adhesion sites, membrane tension and the actin protrusive machinery.

Computing scores of forwarding schemes in switched networks with probabilistic faults - Avni, Guy; Goel, Shubham; Henzinger, Thomas A; Rodríguez Navas, Guillermo
Time-triggered switched networks are a deterministic communication infrastructure used by real-time distributed embedded systems. Due to the criticality of the applications running over them, developers need to ensure that end-to-end communication is dependable and predictable. Traditional approaches assume static networks that are not flexible to changes caused by reconfigurations or, more importantly, faults, which are dealt with in the application using redundancy. We adopt the concept of handling faults in the switches from non-real-time networks while maintaining the required predictability. We study a class of forwarding schemes that can handle various types of failures. We consider probabilistic failures. We study a class of forwarding schemes that can handle various types of failures. We consider probabilistic failures. For a given network with a forwarding scheme and a constant ℓ, we compute the {\em score} of the scheme, namely the probability (induced by faults) that at least ℓ messages arrive on time. We reduce the scoring problem to a reachability problem on a Markov chain with a "product-like" structure. Its special structure allows us to reason about it symbolically, and reduce the scoring problem to #SAT. Our solution is generic and can be adapted to different networks and other contexts. Also, we show the computational complexity of the scoring problem is #P-complete, and we study methods to estimate the score. We evaluate the effectiveness of our techniques with an implementation.

Phase-locked inhibition, but not excitation, underlies hippocampal ripple oscillations in awake mice in vivo - Gan, Jian; Weng, Shih-Ming; Pernia-Andrade, Alejandro; Csicsvari, Jozsef L; Jonas, Peter M (Neuron)
Sharp wave-ripple (SWR) oscillations play a key role in memory consolidation during non-rapid eye movement sleep, immobility, and consummatory behavior. However, whether temporally modulated synaptic excitation or inhibition underlies the ripples is controversial. To address this question, we performed simultaneous recordings of excitatory and inhibitory postsynaptic currents (EPSCs and IPSCs) and local field potentials (LFPs) in the CA1 region of awake mice in vivo. During SWRs, inhibition dominated over excitation, with a peak conductance ratio of 4.1 ± 0.5. Furthermore, the amplitude of SWR-associated IPSCs was positively correlated with SWR magnitude, whereas that of EPSCs was not. Finally, phase analysis indicated that IPSCs were phase-locked to individual ripple cycles, whereas EPSCs were uniformly distributed in phase space. Optogenetic inhibition indicated that PV+ interneurons provided a major contribution to SWR-associated IPSCs. Thus, phasic inhibition, but not excitation, shapes SWR oscillations in the hippocampal CA1 region in vivo.

Synaptotagmin 2 is the fast Ca2+ sensor at a central inhibitory synapse - Chen, Chong; Arai, Itaru; Satterield, Rachel; Young, Samuel; Jonas, Peter M (Cell Reports)
GABAergic synapses in brain circuits generate inhibitory output signals with submillisecond latency and temporal precision. Whether the molecular identity of the release sensor contributes to these signaling properties remains unclear. Here, we examined the Ca^2+ sensor of exocytosis at GABAergic basket cell (BC) to Purkinje cell (PC) synapses in cerebellum. Immunolabeling suggested that BC terminals selectively expressed synaptotagmin 2 (Syt2), whereas synaptotagmin 1 (Syt1) was enriched in excitatory terminals. Genetic elimination of Syt2 reduced action potential-evoked release to ∼10%, identifying Syt2 as the major Ca^2+ sensor at BC-PC synapses. Differential adenovirus-mediated rescue revealed that Syt2 triggered release with shorter latency and higher temporal precision and mediated faster vesicle pool replenishment than Syt1. Furthermore, deletion of Syt2 severely reduced and delayed disynaptic inhibition following parallel fiber stimulation. Thus, the selective use of Syt2 as release sensor at BC-PC synapses ensures fast and efficient feedforward inhibition in cerebellar microcircuits. #bioimagingfacility-author

Superficial layers of the medial entorhinal cortex replay independently of the hippocampus - O'Neill, Joseph; Boccara, Charlotte; Stella, Federico; Schönenberger, Philipp; Csicsvari, Jozsef L (Science)
The hippocampus is thought to initiate systems-wide mnemonic processes through the reactivation of previously acquired spatial and episodic memory traces, which can recruit the entorhinal cortex as a first stage of memory redistribution to other brain areas. Hippocampal reactivation occurs during sharp wave-ripples, in which synchronous network firing encodes sequences of places.We investigated the coordination of this replay by recording assembly activity simultaneously in the CA1 region of the hippocampus and superficial layers of the medial entorhinal cortex. We found that entorhinal cell assemblies can replay trajectories independently of the hippocampus and sharp wave-ripples. This suggests that the hippocampus is not the sole initiator of spatial and episodic memory trace reactivation. Memory systems involved in these processes may include nonhierarchical, parallel components.

Angular self-localization of impurities rotating in a bosonic bath - Li, Xiang; Seiringer, Robert; Lemeshko, Mikhail (Physical Review A)
The existence of a self-localization transition in the polaron problem has been under an active debate ever since Landau suggested it 83 years ago. Here we reveal the self-localization transition for the rotational analogue of the polaron -- the angulon quasiparticle. We show that, unlike for the polarons, self-localization of angulons occurs at finite impurity-bath coupling already at the mean-field level. The transition is accompanied by the spherical-symmetry breaking of the angulon ground state and a discontinuity in the first derivative of the ground-state energy. Moreover, the type of the symmetry breaking is dictated by the symmetry of the microscopic impurity-bath interaction, which leads to a number of distinct self-localized states. The predicted effects can potentially be addressed in experiments on cold molecules trapped in superfluid helium droplets and ultracold quantum gases, as well as on electronic excitations in solids and Bose-Einstein condensates.

Anomalous screening of quantum impurities by a neutral environment - Yakaboylu, Enderalp; Lemeshko, Mikhail (Physical Review Letters)
It is a common knowledge that an effective interaction of a quantum impurity with an electromagnetic field can be screened by surrounding charge carriers, whether mobile or static. Here we demonstrate that very strong, "anomalous" screening can take place in the presence of a neutral, weakly polarizable environment, due to an exchange of orbital angular momentum between the impurity and the bath. Furthermore, we show that it is possible to generalize all phenomena related to isolated impurities in an external field to the case when a many-body environment is present, by casting the problem in terms of the angulon quasiparticle. As a result, the relevant observables such as the effective Rabi frequency, geometric phase, and impurity spatial alignment are straightforward to evaluate in terms of a single parameter: the angular-momentum-dependent screening factor.

Quasiparticle approach to molecules interacting with quantum solvents - Lemeshko, Mikhail (Physical Review Letters)
Understanding the behavior of molecules interacting with superfluid helium represents a formidable challenge and, in general, requires approaches relying on large-scale numerical simulations. Here we demonstrate that experimental data collected over the last 20 years provide evidence that molecules immersed in superfluid helium form recently-predicted angulon quasiparticles [Phys. Rev. Lett. 114, 203001 (2015)]. Most importantly, casting the many-body problem in terms of angulons amounts to a drastic simplification and yields effective molecular moments of inertia as straightforward analytic solutions of a simple microscopic Hamiltonian. The outcome of the angulon theory is in good agreement with experiment for a broad range of molecular impurities, from heavy to medium-mass to light species. These results pave the way to understanding molecular rotation in liquid and crystalline phases in terms of the angulon quasiparticle.

Flavonol-induced changes in PIN2 polarity and auxin transport in the Arabidopsis thaliana rol1-2 mutant require phosphatase activity - Kuhn, Benjamin; Nodzyński, Tomasz; Errafi, Sanae; Bucher, Rahel; Gupta, Shibu; Aryal, Bibek; Dobrev, Petre; Bigler, Laurent; Geisler, Markus; Zažímalová, Eva; Friml, Jirí; Ringli, Christoph (Scientific Reports)
The phytohormone auxin is a major determinant and regulatory component important for plant development. Auxin transport between cells is mediated by a complex system of transporters such as AUX1/LAX, PIN, and ABCB proteins, and their localization and activity is thought to be influenced by phosphatases and kinases. Flavonols have been shown to alter auxin transport activity and changes in flavonol accumulation in the Arabidopsis thaliana rol1-2 mutant cause defects in auxin transport and seedling development. A new mutation in ROOTS CURL IN NPA 1 (RCN1), encoding a regulatory subunit of the phosphatase PP2A, was found to suppress the growth defects of rol1-2 without changing the flavonol content. rol1-2 rcn1-3 double mutants show wild type-like auxin transport activity while levels of free auxin are not affected by rcn1-3. In the rol1-2 mutant, PIN2 shows a flavonol-induced basal-to-apical shift in polar localization which is reversed in the rol1-2 rcn1-3 to basal localization. In vivo analysis of PINOID action, a kinase known to influence PIN protein localization in a PP2A-antagonistic manner, revealed a negative impact of flavonols on PINOID activity. Together, these data suggest that flavonols affect auxin transport by modifying the antagonistic kinase/phosphatase equilibrium.

Multiplexed computations in retinal ganglion cells of a single type - Deny, Stephane; Ferrari, Ulisse; Mace, Emilie; Yger, Pierre; Caplette, Romain; Picaud, Serge; Tkacik, Gasper; Marre, Olivier (Nature Communications)
In the early visual system, cells of the same type perform the same computation in different places of the visual field. How these cells code together a complex visual scene is unclear. A common assumption is that cells of a single-type extract a single-stimulus feature to form a feature map, but this has rarely been observed directly. Using large-scale recordings in the rat retina, we show that a homogeneous population of fast OFF ganglion cells simultaneously encodes two radically different features of a visual scene. Cells close to a moving object code quasilinearly for its position, while distant cells remain largely invariant to the object's position and, instead, respond nonlinearly to changes in the object's speed. We develop a quantitative model that accounts for this effect and identify a disinhibitory circuit that mediates it. Ganglion cells of a single type thus do not code for one, but two features simultaneously. This richer, flexible neural map might also be present in other sensory systems.

Observation of the photon blockade breakdown phase transition - Fink, Johannes M; Dombi, András; Vukics, András; Wallraff, Andreas; Domokos, Peter (Physical Review X)
Nonequilibrium phase transitions exist in damped-driven open quantum systems when the continuous tuning of an external parameter leads to a transition between two robust steady states. In second-order transitions this change is abrupt at a critical point, whereas in first-order transitions the two phases can coexist in a critical hysteresis domain. Here, we report the observation of a first-order dissipative quantum phase transition in a driven circuit quantum electrodynamics system. It takes place when the photon blockade of the driven cavity-atom system is broken by increasing the drive power. The observed experimental signature is a bimodal phase space distribution with varying weights controlled by the drive strength. Our measurements show an improved stabilization of the classical attractors up to the millisecond range when the size of the quantum system is increased from one to three artificial atoms. The formation of such robust pointer states could be used for new quantum measurement schemes or to investigate multiphoton phases of finite-size, nonlinear, open quantum systems.

Selection limits to adaptive walks on correlated landscapes - Heredia, Jorge; Trubenova, Barbora; Sudholt, Dirk; Paixao, Tiago (Genetics)
Adaptation depends critically on the effects of new mutations and their dependency on the genetic background in which they occur. These two factors can be summarized by the fitness landscape. However, it would require testing all mutations in all backgrounds, making the definition and analysis of fitness landscapes mostly inaccessible. Instead of postulating a particular fitness landscape, we address this problem by considering general classes of landscapes and calculating an upper limit for the time it takes for a population to reach a fitness peak, circumventing the need to have full knowledge about the fitness landscape. We analyze populations in the weak-mutation regime and characterize the conditions that enable them to quickly reach the fitness peak as a function of the number of sites under selection. We show that for additive landscapes there is a critical selection strength enabling populations to reach high-fitness genotypes, regardless of the distribution of effects. This threshold scales with the number of sites under selection, effectively setting a limit to adaptation, and results from the inevitable increase in deleterious mutational pressure as the population adapts in a space of discrete genotypes. Furthermore, we show that for the class of all unimodal landscapes this condition is sufficient but not necessary for rapid adaptation, as in some highly epistatic landscapes the critical strength does not depend on the number of sites under selection; effectively removing this barrier to adaptation.

Laser-induced rotation of iodine molecules in helium nanodroplets: Revivals and breaking-free - Shepperson, Benjamin; Søndergaard, Anders; Christiansen, Lars; Kaczmarczyk, Jan; Zillich, Robert; Lemeshko, Mikhail; Stapelfeldt, Henrik (Physical Review Letters)
Rotation of molecules embedded in He nanodroplets is explored by a combination of fs laser-induced alignment experiments and angulon quasiparticle theory. We demonstrate that at low fluence of the fs alignment pulse, the molecule and its solvation shell can be set into coherent collective rotation lasting long enough to form revivals. With increasing fluence, however, the revivals disappear -- instead, rotational dynamics as rapid as for an isolated molecule is observed during the first few picoseconds. Classical calculations trace this phenomenon to transient decoupling of the molecule from its He shell. Our results open novel opportunities for studying non-equilibrium solute-solvent dynamics and quantum thermalization.

Speed and structure of turbulent fronts in pipe flow - Song, Baofang; Barkley, Dwight; Hof, Björn; Avila, Marc (Journal of Fluid Mechanics)
Using extensive direct numerical simulations, the dynamics of laminar-turbulent fronts in pipe flow is investigated for Reynolds numbers between and 5500. We here investigate the physical distinction between the fronts of weak and strong slugs both by analysing the turbulent kinetic energy budget and by comparing the downstream front motion to the advection speed of bulk turbulent structures. Our study shows that weak downstream fronts travel slower than turbulent structures in the bulk and correspond to decaying turbulence at the front. At the downstream front speed becomes faster than the advection speed, marking the onset of strong fronts. In contrast to weak fronts, turbulent eddies are generated at strong fronts by feeding on the downstream laminar flow. Our study also suggests that temporal fluctuations of production and dissipation at the downstream laminar-turbulent front drive the dynamical switches between the two types of front observed up to.

Total positivity in Markov structures - Fallat, Shaun; Lauritzen, Steffen; Sadeghi, Kayvan; Uhler, Caroline; Wermuth, Nanny; Zwiernik, Piotr (Annals of Statistics)
We discuss properties of distributions that are multivariate totally positive of order two (MTP2) related to conditional independence. In particular, we show that any independence model generated by an MTP2 distribution is a compositional semigraphoid which is upward-stable and singleton-transitive. In addition, we prove that any MTP2 distribution satisfying an appropriate support condition is faithful to its concentration graph. Finally, we analyze factorization properties of MTP2 distributions and discuss ways of constructing MTP2 distributions; in particular we give conditions on the log-linear parameters of a discrete distribution which ensure MTP2 and characterize conditional Gaussian distributions which satisfy MTP2.

Reconstructing metastatic seeding patterns of human cancers - Reiter, Johannes; Makohon Moore, Alvin; Gerold, Jeffrey; Božić, Ivana; Chatterjee, Krishnendu; Iacobuzio Donahue, Christine; Vogelstein, Bert; Nowak, Martin (Nature Communications)
Reconstructing the evolutionary history of metastases is critical for understanding their basic biological principles and has profound clinical implications. Genome-wide sequencing data has enabled modern phylogenomic methods to accurately dissect subclones and their phylogenies from noisy and impure bulk tumour samples at unprecedented depth. However, existing methods are not designed to infer metastatic seeding patterns. Here we develop a tool, called Treeomics, to reconstruct the phylogeny of metastases and map subclones to their anatomic locations. Treeomics infers comprehensive seeding patterns for pancreatic, ovarian, and prostate cancers. Moreover, Treeomics correctly disambiguates true seeding patterns from sequencing artifacts; 7% of variants were misclassified by conventional statistical methods. These artifacts can skew phylogenies by creating illusory tumour heterogeneity among distinct samples. In silico benchmarking on simulated tumour phylogenies across a wide range of sample purities (15–95%) and sequencing depths (25-800 × ) demonstrates the accuracy of Treeomics compared with existing methods.

Convergent recombination suppression suggests role of sexual selection in guppy sex chromosome formation - Wright, Alison; Darolti, Iulia; Bloch, Natasha; Oostra, Vicencio; Sandkam, Benjamin; Buechel, Séverine; Kolm, Niclas; Breden, Felix; Vicoso, Beatriz; Mank, Judith (Nature Communications)
Sex chromosomes evolve once recombination is halted between a homologous pair of chromosomes. The dominant model of sex chromosome evolution posits that recombination is suppressed between emerging X and Y chromosomes in order to resolve sexual conflict. Here we test this model using whole genome and transcriptome resequencing data in the guppy, a model for sexual selection with many Y-linked colour traits. We show that although the nascent Y chromosome encompasses nearly half of the linkage group, there has been no perceptible degradation of Y chromosome gene content or activity. Using replicate wild populations with differing levels of sexually antagonistic selection for colour, we also show that sexual selection leads to greater expansion of the non-recombining region and increased Y chromosome divergence. These results provide empirical support for longstanding models of sex chromosome catalysis, and suggest an important role for sexual selection and sexual conflict in genome evolution.

Insulation and wiring specificity of BceR like response regulators and their target promoters in Bacillus subtilis - Fang, Chong; Nagy-Staron, Anna A; Grafe, Martin; Heermann, Ralf; Jung, Kirsten; Gebhard, Susanne; Mascher, Thorsten (Molecular Microbiology)
BceRS and PsdRS are paralogous two-component systems in Bacillus subtilis controlling the response to antimicrobial peptides. In the presence of extracellular bacitracin and nisin, respectively, the two response regulators (RRs) bind their target promoters, PbceA or PpsdA, resulting in a strong up-regulation of target gene expression and ultimately antibiotic resistance. Despite high sequence similarity between the RRs BceR and PsdR and their known binding sites, no cross-regulation has been observed between them. We therefore investigated the specificity determinants of PbceA and PpsdA that ensure the insulation of these two paralogous pathways at the RR–promoter interface. In vivo and in vitro analyses demonstrate that the regulatory regions within these two promoters contain three important elements: in addition to the known (main) binding site, we identified a linker region and a secondary binding site that are crucial for functionality. Initial binding to the high-affinity, low-specificity main binding site is a prerequisite for the subsequent highly specific binding of a second RR dimer to the low-affinity secondary binding site. In addition to this hierarchical cooperative binding, discrimination requires a competition of the two RRs for their respective binding site mediated by only slight differences in binding affinities.

Nonexistence in Thomas Fermi-Dirac-von Weizsäcker theory with small nuclear charges - Nam, Phan; Van Den Bosch, Hanne (Mathematical Physics, Analysis and Geometry)
We study the ionization problem in the Thomas-Fermi-Dirac-von Weizsäcker theory for atoms and molecules. We prove the nonexistence of minimizers for the energy functional when the number of electrons is large and the total nuclear charge is small. This nonexistence result also applies to external potentials decaying faster than the Coulomb potential. In the case of arbitrary nuclear charges, we obtain the nonexistence of stable minimizers and radial minimizers.

Evolutionary interplay between structure, energy and epistasis in the coat protein of the ϕX174 phage family - Fernandes Redondo, Rodrigo A; Vladar, Harold; Włodarski, Tomasz; Bollback, Jonathan P (Journal of the Royal Society Interface)
Viral capsids are structurally constrained by interactions among the amino acids (AAs) of their constituent proteins. Therefore, epistasis is expected to evolve among physically interacting sites and to influence the rates of substitution. To study the evolution of epistasis, we focused on the major structural protein of the fX174 phage family by first reconstructing the ancestral protein sequences of 18 species using a Bayesian statistical framework. The inferred ancestral reconstruction differed at eight AAs, for a total of 256 possible ancestral haplotypes. For each ancestral haplotype and the extant species, we estimated, in silico, the distribution of free energies and epistasis of the capsid structure. We found that free energy has not significantly increased but epistasis has. We decomposed epistasis up to fifth order and found that higher-order epistasis sometimes compensates pairwise interactions making the free energy seem additive. The dN/dS ratio is low, suggesting strong purifying selection, and that structure is under stabilizing selection. We synthesized phages carrying ancestral haplotypes of the coat protein gene and measured their fitness experimentally. Our findings indicate that stabilizing mutations can have higher fitness, and that fitness optima do not necessarily coincide with energy minima.

The physical basis of coordinated tissue spreading in zebrafish gastrulation - Morita, Hitoshi; Grigolon, Silvia; Bock, Martin; Krens, Gabriel; Salbreux, Guillaume; Heisenberg, Carl-Philipp J (Developmental Cell)
Embryo morphogenesis relies on highly coordinated movements of different tissues. However, remarkably little is known about how tissues coordinate their movements to shape the embryo. In zebrafish embryogenesis, coordinated tissue movements first become apparent during “doming,” when the blastoderm begins to spread over the yolk sac, a process involving coordinated epithelial surface cell layer expansion and mesenchymal deep cell intercalations. Here, we find that active surface cell expansion represents the key process coordinating tissue movements during doming. By using a combination of theory and experiments, we show that epithelial surface cells not only trigger blastoderm expansion by reducing tissue surface tension, but also drive blastoderm thinning by inducing tissue contraction through radial deep cell intercalations. Thus, coordinated tissue expansion and thinning during doming relies on surface cells simultaneously controlling tissue surface tension and radial tissue contraction.

Inferring recent demography from isolation by distance of long shared sequence blocks - Ringbauer, Harald; Coop, Graham; Barton, Nicholas H (Genetics)
Recently it has become feasible to detect long blocks of nearly identical sequence shared between pairs of genomes. These IBD blocks are direct traces of recent coalescence events and, as such, contain ample signal to infer recent demography. Here, we examine sharing of such blocks in two-dimensional populations with local migration. Using a diffusion approximation to trace genetic ancestry, we derive analytical formulae for patterns of isolation by distance of IBD blocks, which can also incorporate recent population density changes. We introduce an inference scheme that uses a composite likelihood approach to fit these formulae. We then extensively evaluate our theory and inference method on a range of scenarios using simulated data. We first validate the diffusion approximation by showing that the theoretical results closely match the simulated block sharing patterns. We then demonstrate that our inference scheme can accurately and robustly infer dispersal rate and effective density, as well as bounds on recent dynamics of population density. To demonstrate an application, we use our estimation scheme to explore the fit of a diffusion model to Eastern European samples in the POPRES data set. We show that ancestry diffusing with a rate of σ ≈ 50–100 km/√gen during the last centuries, combined with accelerating population growth, can explain the observed exponential decay of block sharing with increasing pairwise sample distance.

Strong-field ionization via a high-order Coulomb-corrected strong-field approximation - Klaiber, Michael; Daněk, Jiří; Yakaboylu, Enderalp; Hatsagortsyan, Karen; Keitel, Christoph (Physical Review A - Atomic, Molecular, and Optical Physics)
Signatures of the Coulomb corrections in the photoelectron momentum distribution during laser-induced ionization of atoms or ions in tunneling and multiphoton regimes are investigated analytically in the case of a one-dimensional problem. A high-order Coulomb-corrected strong-field approximation is applied, where the exact continuum state in the S matrix is approximated by the eikonal Coulomb-Volkov state including the second-order corrections to the eikonal. Although without high-order corrections our theory coincides with the known analytical R-matrix (ARM) theory, we propose a simplified procedure for the matrix element derivation. Rather than matching the eikonal Coulomb-Volkov wave function with the bound state as in the ARM theory to remove the Coulomb singularity, we calculate the matrix element via the saddle-point integration method by time as well as by coordinate, and in this way avoiding the Coulomb singularity. The momentum shift in the photoelectron momentum distribution with respect to the ARM theory due to high-order corrections is analyzed for tunneling and multiphoton regimes. The relation of the quantum corrections to the tunneling delay time is discussed.

The Morse theory of Čech and delaunay complexes - Bauer, Ulrich; Edelsbrunner, Herbert (Transactions of the American Mathematical Society)
Given a finite set of points in Rn and a radius parameter, we study the Čech, Delaunay–Čech, Delaunay (or alpha), and Wrap complexes in the light of generalized discrete Morse theory. Establishing the Čech and Delaunay complexes as sublevel sets of generalized discrete Morse functions, we prove that the four complexes are simple-homotopy equivalent by a sequence of simplicial collapses, which are explicitly described by a single discrete gradient field.

Algorithmic solvability of the lifting extension problem - Čadek, Martin; Krcál, Marek; Vokřínek, Lukáš (Discrete & Computational Geometry)
Let X and Y be finite simplicial sets (e.g. finite simplicial complexes), both equipped with a free simplicial action of a finite group G. Assuming that Y is d-connected and dimX≤2d, for some d≥1, we provide an algorithm that computes the set of all equivariant homotopy classes of equivariant continuous maps |X|→|Y|; the existence of such a map can be decided even for dimX≤2d+1. This yields the first algorithm for deciding topological embeddability of a k-dimensional finite simplicial complex into Rn under the condition k≤23n−1. More generally, we present an algorithm that, given a lifting-extension problem satisfying an appropriate stability assumption, computes the set of all homotopy classes of solutions. This result is new even in the non-equivariant situation.

Pushdown reachability with constant treewidth - Chatterjee, Krishnendu; Osang, Georg F (Information Processing Letters)
We consider the problem of reachability in pushdown graphs. We study the problem for pushdown graphs with constant treewidth. Even for pushdown graphs with treewidth 1, for the reachability problem we establish the following: (i) the problem is PTIME-complete, and (ii) any subcubic algorithm for the problem would contradict the k-clique conjecture and imply faster combinatorial algorithms for cliques in graphs.

Evolutionary rescue in randomly mating, selfing, and clonal populations - Uecker, Hildegard (Evolution)
Severe environmental change can drive a population extinct unless the population adapts in time to the new conditions (“evolutionary rescue”). How does biparental sexual reproduction influence the chances of population persistence compared to clonal reproduction or selfing? In this article, we set up a one‐locus two‐allele model for adaptation in diploid species, where rescue is contingent on the establishment of the mutant homozygote. Reproduction can occur by random mating, selfing, or clonally. Random mating generates and destroys the rescue mutant; selfing is efficient at generating it but at the same time depletes the heterozygote, which can lead to a low mutant frequency in the standing genetic variation. Due to these (and other) antagonistic effects, we find a nontrivial dependence of population survival on the rate of sex/selfing, which is strongly influenced by the dominance coefficient of the mutation before and after the environmental change. Importantly, since mating with the wild‐type breaks the mutant homozygote up, a slow decay of the wild‐type population size can impede rescue in randomly mating populations.

Quantitative fair simulation games - Chatterjee, Krishnendu; Henzinger, Thomas A; Otop, Jan; Velner, Yaron (Information and Computation)
Simulation is an attractive alternative to language inclusion for automata as it is an under-approximation of language inclusion, but usually has much lower complexity. Simulation has also been extended in two orthogonal directions, namely, (1) fair simulation, for simulation over specified set of infinite runs; and (2) quantitative simulation, for simulation between weighted automata. While fair trace inclusion is PSPACE-complete, fair simulation can be computed in polynomial time. For weighted automata, the (quantitative) language inclusion problem is undecidable in general, whereas the (quantitative) simulation reduces to quantitative games, which admit pseudo-polynomial time algorithms. In this work, we study (quantitative) simulation for weighted automata with Büchi acceptance conditions, i.e., we generalize fair simulation from non-weighted automata to weighted automata. We show that imposing Büchi acceptance conditions on weighted automata changes many fundamental properties of the simulation games, yet they still admit pseudo-polynomial time algorithms.

Local law for the product of independent non-Hermitian random matrices with independent entries - Nemish, Yuriy (Electronic Journal of Probability)
We consider products of independent square non-Hermitian random matrices. More precisely, let X1,…, Xn be independent N × N random matrices with independent entries (real or complex with independent real and imaginary parts) with zero mean and variance 1/N. Soshnikov-O’Rourke [19] and Götze-Tikhomirov [15] showed that the empirical spectral distribution of the product of n random matrices with iid entries converges to (equation found). We prove that if the entries of the matrices X1,…, Xn are independent (but not necessarily identically distributed) and satisfy uniform subexponential decay condition, then in the bulk the convergence of the ESD of X1,…, Xn to (0.1) holds up to the scale N–1/2+ε.

The topology of the cosmic web in terms of persistent Betti numbers - Pranav, Pratyush; Edelsbrunner, Herbert; Van De Weygaert, Rien; Vegter, Gert; Kerber, Michael; Jones, Bernard; Wintraecken, Mathijs (Monthly Notices of the Royal Astronomical Society)
We introduce a multiscale topological description of the Megaparsec web-like cosmic matter distribution. Betti numbers and topological persistence offer a powerful means of describing the rich connectivity structure of the cosmic web and of its multiscale arrangement of matter and galaxies. Emanating from algebraic topology and Morse theory, Betti numbers and persistence diagrams represent an extension and deepening of the cosmologically familiar topological genus measure and the related geometric Minkowski functionals. In addition to a description of the mathematical background, this study presents the computational procedure for computing Betti numbers and persistence diagrams for density field filtrations. The field may be computed starting from a discrete spatial distribution of galaxies or simulation particles. The main emphasis of this study concerns an extensive and systematic exploration of the imprint of different web-like morphologies and different levels of multiscale clustering in the corresponding computed Betti numbers and persistence diagrams. To this end, we use Voronoi clustering models as templates for a rich variety of web-like configurations and the fractal-like Soneira-Peebles models exemplify a range of multiscale configurations. We have identified the clear imprint of cluster nodes, filaments, walls, and voids in persistence diagrams, along with that of the nested hierarchy of structures in multiscale point distributions. We conclude by outlining the potential of persistent topology for understanding the connectivity structure of the cosmic web, in large simulations of cosmic structure formation and in the challenging context of the observed galaxy distribution in large galaxy surveys.

Optogenetic methods in drug screening: Technologies and applications - Agus, Viviana; Janovjak, Harald L (Current Opinion in Biotechnology)
The optogenetic revolution enabled spatially-precise and temporally-precise control over protein function, signaling pathway activation, and animal behavior with tremendous success in the dissection of signaling networks and neural circuits. Very recently, optogenetic methods have been paired with optical reporters in novel drug screening platforms. In these all-optical platforms, light remotely activated ion channels and kinases thereby obviating the use of electrophysiology or reagents. Consequences were remarkable operational simplicity, throughput, and cost-effectiveness that culminated in the identification of new drug candidates. These blueprints for all-optical assays also revealed potential pitfalls and inspire all-optical variants of other screens, such as those that aim at better understanding dynamic drug action or orphan protein function.

Disordered cellulose based nanostructures for enhanced light scattering - Caixeiro, Soraya; Peruzzo, Matilda; Onelli, Olimpia; Vignolini, Silvia; Sapienza, Riccardo (ACS Applied Materials and Interfaces)
Cellulose is the most abundant biopolymer on Earth. Cellulose fibers, such as the one extracted form cotton or woodpulp, have been used by humankind for hundreds of years to make textiles and paper. Here we show how, by engineering light-matter interaction, we can optimize light scattering using exclusively cellulose nanocrystals. The produced material is sustainable, biocompatible, and when compared to ordinary microfiber-based paper, it shows enhanced scattering strength (×4), yielding a transport mean free path as low as 3.5 μm in the visible light range. The experimental results are in a good agreement with the theoretical predictions obtained with a diffusive model for light propagation.

Boundary layer turbulence in experiments on quasi Keplerian flows - Lopez Alonso, Jose M; Avila, Marc (Journal of Fluid Mechanics)
Most flows in nature and engineering are turbulent because of their large velocities and spatial scales. Laboratory experiments on rotating quasi-Keplerian flows, for which the angular velocity decreases radially but the angular momentum increases, are however laminar at Reynolds numbers exceeding one million. This is in apparent contradiction to direct numerical simulations showing that in these experiments turbulence transition is triggered by the axial boundaries. We here show numerically that as the Reynolds number increases, turbulence becomes progressively confined to the boundary layers and the flow in the bulk fully relaminarizes. Our findings support that turbulence is unlikely to occur in isothermal constant-density quasi-Keplerian flows.

Cell biology: Stretched divisions - Heisenberg, Carl-Philipp J (Nature)
Many organ surfaces are covered by a protective epithelial-cell layer. It emerges that such layers are maintained by cell stretching that triggers cell division mediated by the force-sensitive ion-channel protein Piezo1. See Letter p.118

Tubulins and brain development: The origins of functional specification - Breuss, Martin; Leca, Ines; Gstrein, Thomas; Hansen, Andi H; Keays, David (Molecular and Cellular Neuroscience)
The development of the vertebrate central nervous system is reliant on a complex cascade of biological processes that include mitotic division, relocation of migrating neurons, and the extension of dendritic and axonal processes. Each of these cellular events requires the diverse functional repertoire of the microtubule cytoskeleton for the generation of forces, assembly of macromolecular complexes and transport of molecules and organelles. The tubulins are a multi-gene family that encode for the constituents of microtubules, and have been implicated in a spectrum of neurological disorders. Evidence is building that different tubulins tune the functional properties of the microtubule cytoskeleton dependent on the cell type, developmental profile and subcellular localisation. Here we review of the origins of the functional specification of the tubulin gene family in the developing brain at a transcriptional, translational, and post-transcriptional level. We remind the reader that tubulins are not just loading controls for your average Western blot.

Vortices and antivortices in two-dimensional ultracold Fermi gases - Bighin, Giacomo; Salasnich, Luca (Scientific Reports)
Vortices are commonly observed in the context of classical hydrodynamics: from whirlpools after stirring the coffee in a cup to a violent atmospheric phenomenon such as a tornado, all classical vortices are characterized by an arbitrary circulation value of the local velocity field. On the other hand the appearance of vortices with quantized circulation represents one of the fundamental signatures of macroscopic quantum phenomena. In two-dimensional superfluids quantized vortices play a key role in determining finite-temperature properties, as the superfluid phase and the normal state are separated by a vortex unbinding transition, the Berezinskii-Kosterlitz-Thouless transition. Very recent experiments with two-dimensional superfluid fermions motivate the present work: we present theoretical results based on the renormalization group showing that the universal jump of the superfluid density and the critical temperature crucially depend on the interaction strength, providing a strong benchmark for forthcoming investigations.

Uner Tan syndrome caused by a homozygous TUBB2B mutation affecting microtubule stability - Breuss, Martin; Nguyen, Thai; Srivatsan, Anjana; Leca, Ines; Tian, Guoling; Fritz, Tanja; Hansen, Andi H; Musaev, Damir; Mcevoy Venneri, Jennifer; Kiely, James; Rosti, Rasim; Scott, Eric; et al. (Human Molecular Genetics)
The integrity and dynamic properties of the microtubule cytoskeleton are indispensable for the development of the mammalian brain. Consequently, mutations in the genes that encode the structural component (the α/β-tubulin heterodimer) can give rise to severe, sporadic neurodevelopmental disorders. These are commonly referred to as the tubulinopathies. Here we report the addition of recessive quadrupedalism, also known as Uner Tan syndrome (UTS), to the growing list of diseases caused by tubulin variants. Analysis of a consanguineous UTS family identified a biallelic TUBB2B mutation, resulting in a p.R390Q amino acid substitution. In addition to the identifying quadrupedal locomotion, all three patients showed severe cerebellar hypoplasia. None, however, displayed the basal ganglia malformations typically associated with TUBB2B mutations. Functional analysis of the R390Q substitution revealed that it did not affect the ability of β-tubulin to fold or become assembled into the α/β-heterodimer, nor did it influence the incorporation of mutant-containing heterodimers into microtubule polymers. The 390Q mutation in S. cerevisiae TUB2 did not affect growth under basal conditions, but did result in increased sensitivity to microtubule-depolymerizing drugs, indicative of a mild impact of this mutation on microtubule function. The TUBB2B mutation described here represents an unusual recessive mode of inheritance for missense-mediated tubulinopathies and reinforces the sensitivity of the developing cerebellum to microtubule defects.

Light regulated expression of sensor histidine kinase CKI1 controls cytokinin related development - Dobisova, Tereza; Hrdinova, Vendula; Cuesta, Candela; Michlickova, Sarka; Urbankova, Ivana; Hejatkova, Romana; Zadnikova, Petra; Pernisová, Markéta; Benková, Eva; Hejátko, Jan (Plant Physiology)
In plants, the multistep phosphorelay (MSP) pathway mediates a range of regulatory processes, including those activated by cytokinins. The crosstalk between cytokinin response and light is known for a long time. However, the molecular mechanism underlying the interactionbetween light and cytokinin signaling remains elusive. In the screen for upstream regulators we identified a LONG PALE HYPOCOTYL (LPH) gene whose activity is indispensable for spatiotemporally correct expression of CYTOKININ INDEPENDENT-1 (CKI1), encoding the constitutively active sensor histidine kinase that activates MSP signaling. lph is a new allele of HEME OXYGENASE 1 (HY1) which encodes the key protein in the biosynthesis of phytochromobilin, a cofactor of photoconvertiblephytochromes. Our analysis confirmed the light-dependent regulation oftheCKI1 expression pattern. We show that CKI1 expression is under the control of phytochrome A (phyA), functioning as a dual (both positive and negative) regulator of CKI1 expression, presumably via the phyA-regulated transcription factors PHYTOCHROME INTERACTING FACTOR 3 (PIF3) and CIRCADIAN CLOCK ASSOCIATED 1 (CCA1). Changes in CKI1 expression observed in lph/hy1-7 and phy mutants correlatewithmisregulation of MSP signaling, changedcytokinin sensitivity and developmental aberrations,previously shown to be associated with cytokinin and/or CKI1 action. Besides that, we demonstrate novel role of phyA-dependent CKI1 expression in the hypocotyl elongation and hook development during skotomorphogenesis. Based on these results, we propose that the light-dependent regulation of CKI1 provides a plausible mechanistic link underlying the well-known interaction between light- and cytokinin-controlled plant development.

X-linkage is not a general inhibitor of tissue-specific gene expression in Drosophila melanogaster - Argyridou, Eliza; Huylmans, Ann K; Königer, Annabella; Parsch, John (Heredity)
As a consequence of its difference in copy number between males and females, the X chromosome is subject to unique evolutionary forces and gene regulatory mechanisms. Previous studies of Drosophila melanogaster have shown that the expression of X-linked, testis-specific reporter genes is suppressed in the male germline. However, it is not known whether this phenomenon is restricted to testis-expressed genes or if it is a more general property of genes with tissue-specific expression, which are also underrepresented on the X chromosome. To test this, we compared the expression of three tissue-specific reporter genes (ovary, accessory gland and Malpighian tubule) inserted at various autosomal and X-chromosomal locations. In contrast to testis-specific reporter genes, we found no reduction of X-linked expression in any of the other tissues. In accessory gland and Malpighian tubule, we detected higher expression of the X-linked reporter genes, which suggests that they are at least partially dosage compensated. We found no difference in the tissue-specificity of X-linked and autosomal reporter genes. These findings indicate that, in general, the X chromosome is not a detrimental environment for tissue-specific gene expression and that the suppression of X-linked expression is limited to the male germline.

Data from: X-linkage is not a general inhibitor of tissue-specific gene expression in Drosophila melanogaster - Argyridou, Eliza; Huylmans, Ann K; Königer, Annabella; Parsch, John
As a consequence of its difference in copy number between males and females, the X chromosome is subject to unique evolutionary forces and gene regulatory mechanisms. Previous studies of Drosophila melanogaster have shown that the expression of X-linked, testis-specific reporter genes is suppressed in the male germline. However, it is not known whether this phenomenon is restricted to testis-expressed genes or if it is a more general property of genes with tissue-specific expression, which are also underrepresented on the X chromosome. To test this, we compared the expression of three tissue-specific reporter genes (ovary, accessory gland and Malpighian tubule) inserted at various autosomal and X-chromosomal locations. In contrast to testis-specific reporter genes, we found no reduction of X-linked expression in any of the other tissues. In accessory gland and Malpighian tubule, we detected higher expression of the X-linked reporter genes, which suggests that they are at least partially dosage compensated. We found no difference in the tissue-specificity of X-linked and autosomal reporter genes. These findings indicate that, in general, the X chromosome is not a detrimental environment for tissue-specific gene expression and that the suppression of X-linked expression is limited to the male germline.

Oral immune priming with Bacillus thuringiensis induces a shift in the gene expression of Tribolium castaneum larvae - Greenwood, Jenny; Milutinovic, Barbara; Peuß, Robert; Behrens, Sarah; Essar, Daniela; Rosenstiel, Philip; Schulenburg, Hinrich; Kurtz, Joachim (BMC Genomics)
Background: The phenomenon of immune priming, i.e. enhanced protection following a secondary exposure to a pathogen, has now been demonstrated in a wide range of invertebrate species. Despite accumulating phenotypic evidence, knowledge of its mechanistic underpinnings is currently very limited. Here we used the system of the red flour beetle, Tribolium castaneum and the insect pathogen Bacillus thuringiensis (Bt) to further our molecular understanding of the oral immune priming phenomenon. We addressed how ingestion of bacterial cues (derived from spore supernatants) of an orally pathogenic and non-pathogenic Bt strain affects gene expression upon later challenge exposure, using a whole-transcriptome sequencing approach. Results: Whereas gene expression of individuals primed with the orally non-pathogenic strain showed minor changes to controls, we found that priming with the pathogenic strain induced regulation of a large set of distinct genes, many of which are known immune candidates. Intriguingly, the immune repertoire activated upon priming and subsequent challenge qualitatively differed from the one mounted upon infection with Bt without previous priming. Moreover, a large subset of priming-specific genes showed an inverse regulation compared to their regulation upon challenge only. Conclusions: Our data demonstrate that gene expression upon infection is strongly affected by previous immune priming. We hypothesise that this shift in gene expression indicates activation of a more targeted and efficient response towards a previously encountered pathogen, in anticipation of potential secondary encounter.

Faster algorithms for weighted recursive state machines - Chatterjee, Krishnendu; Kragl, Bernhard; Mishra, Samarth; Pavlogiannis, Andreas
Pushdown systems (PDSs) and recursive state machines (RSMs), which are linearly equivalent, are standard models for interprocedural analysis. Yet RSMs are more convenient as they (a) explicitly model function calls and returns, and (b) specify many natural parameters for algorithmic analysis, e.g., the number of entries and exits. We consider a general framework where RSM transitions are labeled from a semiring and path properties are algebraic with semiring operations, which can model, e.g., interprocedural reachability and dataflow analysis problems. Our main contributions are new algorithms for several fundamental problems. As compared to a direct translation of RSMs to PDSs and the best-known existing bounds of PDSs, our analysis algorithm improves the complexity for finite-height semirings (that subsumes reachability and standard dataflow properties). We further consider the problem of extracting distance values from the representation structures computed by our algorithm, and give efficient algorithms that distinguish the complexity of a one-time preprocessing from the complexity of each individual query. Another advantage of our algorithm is that our improvements carry over to the concurrent setting, where we improve the bestknown complexity for the context-bounded analysis of concurrent RSMs. Finally, we provide a prototype implementation that gives a significant speed-up on several benchmarks from the SLAM/SDV project.

Spatiotemporal mechanisms of root branching - Ötvös, Krisztina; Benková, Eva (Current Opinion in Genetics & Development)
The fundamental tasks of the root system are, besides anchoring, mediating interactions between plant and soil and providing the plant with water and nutrients. The architecture of the root system is controlled by endogenous mechanisms that constantly integrate environmental signals, such as availability of nutrients and water. Extremely important for efficient soil exploitation and survival under less favorable conditions is the developmental flexibility of the root system that is largely determined by its postembryonic branching capacity. Modulation of initiation and outgrowth of lateral roots provides roots with an exceptional plasticity, allows optimal adjustment to underground heterogeneity, and enables effective soil exploitation and use of resources. Here we discuss recent advances in understanding the molecular mechanisms that shape the plant root system and integrate external cues to adapt to the changing environment.

Local law for random Gram matrices - Alt, Johannes; Erdös, László; Krüger, Torben H (Electronic Journal of Probability)
We prove a local law in the bulk of the spectrum for random Gram matrices XX∗, a generalization of sample covariance matrices, where X is a large matrix with independent, centered entries with arbitrary variances. The limiting eigenvalue density that generalizes the Marchenko-Pastur law is determined by solving a system of nonlinear equations. Our entrywise and averaged local laws are on the optimal scale with the optimal error bounds. They hold both in the square case (hard edge) and in the properly rectangular case (soft edge). In the latter case we also establish a macroscopic gap away from zero in the spectrum of XX∗.

Optimizing expectation with guarantees in POMDPs - Chatterjee, Krishnendu; Novotny, Petr; Pérez, Guillermo; Raskin, Jean; Zikelic, Djordje (Proceedings of the 31st AAAI Conference on Artificial Intelligence)
A standard objective in partially-observable Markov decision processes (POMDPs) is to find a policy that maximizes the expected discounted-sum payoff. However, such policies may still permit unlikely but highly undesirable outcomes, which is problematic especially in safety-critical applications. Recently, there has been a surge of interest in POMDPs where the goal is to maximize the probability to ensure that the payoff is at least a given threshold, but these approaches do not consider any optimization beyond satisfying this threshold constraint. In this work we go beyond both the “expectation” and “threshold” approaches and consider a “guaranteed payoff optimization (GPO)” problem for POMDPs, where we are given a threshold t and the objective is to find a policy σ such that a) each possible outcome of σ yields a discounted-sum payoff of at least t, and b) the expected discounted-sum payoff of σ is optimal (or near-optimal) among all policies satisfying a). We present a practical approach to tackle the GPO problem and evaluate it on standard POMDP benchmarks.

Additional file 1: Table S1. of Oral immune priming with Bacillus thuringiensis induces a shift in the gene expression of Tribolium castaneum larvae - Greenwood, Jenny; Milutinovic, Barbara; Peuß, Robert; Behrens, Sarah; Essar, Daniela; Rosenstiel, Philip; Schulenburg, Hinrich; Kurtz, Joachim
Lists of all differentially expressed genes in the different priming-challenge treatments (compared to the fully naïve control; xlsx file). Relevant columns include the following: sample_1 and sample_2 – treatment groups being compared; Normalised FPKM sample_1 and sample_2 – FPKM of samples being compared; log2(fold_change) – log2(FPKM sample 2/FPKM sample 1), i.e. negative means sample 1 upregulated compared with sample 2, positive means sample 2 upregulated compared with sample 1; cuffdiff test_statistic – test statistic of differential expression test; p_value – p-value of differential expression test; q_value (FDR correction) – adjusted P-value of differential expression test. (XLSX 598 kb)

Additional file 5: Table S3. of Oral immune priming with Bacillus thuringiensis induces a shift in the gene expression of Tribolium castaneum larvae - Greenwood, Jenny; Milutinovic, Barbara; Peuß, Robert; Behrens, Sarah; Essar, Daniela; Rosenstiel, Philip; Schulenburg, Hinrich; Kurtz, Joachim